Resin Sheet

The resin sheet with a specific composition addresses the challenge of achieving high magnetic permeability and mechanical strength in inductor-embedded substrates by using a resin composition with magnetic powder, epoxy resin, and a dispersant with a polyester skeleton, resulting in improved performance for circuit boards and inductor components.

JP7619247B2Active Publication Date: 2025-01-22AJINOMOTO CO INC
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021191558
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-25
Publication Date
2025-01-22
Estimated Expiration
2041-11-25

AI Technical Summary

Technical Problem

Existing inductor-embedded substrates face challenges in achieving high relative magnetic permeability and mechanical strength without compromising magnetic loss, as increasing magnetic powder content or particle size affects mechanical strength or magnetic performance.

Method used

A resin sheet comprising a support and a resin composition layer with specific components, including magnetic powder, epoxy resin, dispersant with a polyester skeleton, curing agent, and thermoplastic resin, which enhances both magnetic permeability and mechanical strength.

Benefits of technology

The resin sheet provides a cured product with high relative magnetic permeability, excellent mechanical strength, and reduced magnetic loss, suitable for use in circuit boards and inductor components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619247000012
    Figure 0007619247000012
  • Figure 0007619247000013
    Figure 0007619247000013
  • Figure 0007619247000014
    Figure 0007619247000014
Patent Text Reader

Abstract

To provide a resin sheet capable of obtaining a cured material high in relative permeability, and excellent in mechanical strength.SOLUTION: A resin sheet has a support and a resin composition layer formed of a resin composition provided on the support. The resin composition comprises (A) magnetic powder, (B) an epoxy resin, (C) a dispersant, (D) a curing agent, and (E) a thermoplastic resin. The component (C) has a polyester skeleton represented by the following general formula (1). In general formula (1), each R independently represents a divalent hydrocarbon group having 2 to 10 carbon atoms, and n represents an integer of 2 to 1,000.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin sheet, a resin composition, and a circuit board and an inductor component using the resin sheet or the resin composition. [Background technology]

[0002] Inductor-embedded substrates, which incorporate an inductor in a circuit board such as a printed wiring board, are generally formed using a resin composition containing magnetic powder. Known methods for increasing the inductance of the inductor included in the inductor-embedded substrate are to increase the content of magnetic powder in the resin composition or to increase the effective permeability of the magnetic layer, which is a cured product of the resin composition.

[0003] For example, Patent Document 1 describes a resin sheet that is highly filled with magnetic filler having an average particle size of 10 μm or more. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2014-127624 A Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, there has been a demand for even greater inductance. One way to increase the relative permeability of an inductor is to increase the magnetic powder content, but increasing the magnetic powder content can reduce the mechanical strength (tensile breaking strength) of the magnetic layer.

[0006] To increase the relative magnetic permeability, it is possible to use magnetic powder with a large average particle size or flat magnetic powder, but the use of such magnetic powder increases magnetic loss and may degrade the performance of the inductor. It is also possible to use magnetic powder with a small average particle size, but the use of such magnetic powder tends to reduce magnetic loss but tends to reduce the relative magnetic permeability.

[0007] The present invention has been made in consideration of the above circumstances, and has an object to provide a resin sheet and a resin composition that can give a cured product having high relative permeability and excellent mechanical strength, and a circuit board and an inductor component that use the resin sheet or the resin composition. [Means for solving the problem]

[0008] As a result of intensive research to achieve the above-mentioned object, the inventors have discovered that by using a resin sheet including a resin composition layer formed from a resin composition containing a dispersant having a polyester skeleton, the cured product of the resin composition layer has high relative permeability and excellent mechanical strength, and have thus completed the present invention.

[0009] That is, the present invention includes the following. [1] A resin sheet having a support and a resin composition layer formed from a resin composition provided on the support, The resin composition comprises: (A) Magnetic powder, (B) epoxy resin, (C) a dispersant, (D) a curing agent, and (E) a thermoplastic resin, A resin sheet, in which the component (C) has a polyester skeleton represented by the following general formula (1): [ka] (In general formula (1), R each independently represents a divalent hydrocarbon group having 2 to 10 carbon atoms, and n represents an integer of 2 to 1000.) [2] The resin sheet according to [1], wherein the content of the component (C) is 0.1% by mass or more and 5% by mass or less, based on 100% by mass of the non-volatile components in the resin composition. [3] The resin sheet according to [1] or [2], wherein the component (A) contains (A-1) a magnetic powder having an average particle size of 1 μm or more, and (A-2) a magnetic powder having an average particle size of less than 1 μm. [4] The resin sheet according to any one of [1] to [3], wherein the component (A) includes (A-1) a magnetic powder having an average particle size of 1 μm or more and 10 μm or less, and (A-2) a magnetic powder having an average particle size of 0.005 μm or more and less than 1 μm. [5] The resin sheet according to any one of [1] to [4], wherein the component (A) is at least one selected from the group consisting of iron oxide powder and iron alloy metal powder. [6] The resin sheet according to any one of [1] to [5], wherein the component (A) contains iron oxide powder, and the iron oxide powder contains ferrite containing at least one selected from Ni, Cu, Mn, and Zn. [7] The resin sheet according to any one of [1] to [6], wherein the content of the component (A) is 70% by mass or more and 98% by mass or less, when the total amount of non-volatile components in the resin composition is 100% by mass. [8] The resin sheet according to any one of [1] to [7], wherein the mass of the thermoplastic resin (E) when the nonvolatile components in the resin composition are 100 mass% is E1, and the mass of the epoxy resin (B) when the nonvolatile components in the resin composition are 100 mass% is B1, and B1 / E1 is 0.1 or more and 5 or less. [9] The resin sheet according to any one of [1] to [8], which is for forming a magnetic layer of a circuit board.

[10] The resin sheet according to any one of [1] to [9], which is for filling through-holes.

[11] A circuit board comprising a magnetic layer which is a cured product of a resin composition layer of a resin sheet according to any one of [1] to

[10] .

[12] A substrate having a through hole formed therein, and a magnetic layer filled in the through hole, A circuit board, wherein the magnetic layer comprises a cured product of a resin composition layer of the resin sheet according to any one of [1] to

[10] .

[13] An inductor component comprising the circuit board according to

[11] or

[12] .

[14] (A) Magnetic powder, (B) epoxy resin, (C) a dispersant, (D) a curing agent, and (E) A resin composition containing a thermoplastic resin, when the mass of the (E) thermoplastic resin is defined as E1 when the nonvolatile components in the resin composition are 100% by mass, and the mass of the (B) epoxy resin is defined as B1 when the nonvolatile components in the resin composition are 100% by mass, B1 / E1 is 0.1 or more and 5 or less, A resin composition, wherein component (C) has a polyester skeleton represented by the following general formula (1): [ka] (In general formula (1), R each independently represents a divalent hydrocarbon group having 2 to 10 carbon atoms, and n represents an integer of 2 to 1000.)

[15] A circuit board comprising a magnetic layer which is a cured product of the resin composition described in

[14] .

[16] A circuit board comprising a substrate having a through-hole, and a cured product of the resin composition according to

[14] filled in the through-hole.

[17] An inductor component comprising the circuit board according to

[15] or

[16] . Effect of the Invention

[0010] According to the present invention, it is possible to provide a resin sheet which can give a cured product having high relative magnetic permeability and excellent mechanical strength, and a circuit board and an inductor component which use the resin sheet. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a cross-sectional view that typically shows a core substrate before through holes are formed in the core substrate in the method for manufacturing a circuit board according to the first embodiment. [Diagram 2]FIG. 2 is a cross-sectional view that typically shows a core base material in which a through hole is formed in the method for manufacturing a circuit board according to the first embodiment. [Diagram 3] FIG. 3 is a cross-sectional view that typically shows a core base material having a plating layer formed in a through-hole in the method for manufacturing a circuit board according to the first embodiment. [Figure 4] FIG. 4 is a cross-sectional view that typically shows a state in which a core base material and a resin sheet are laminated in the method for manufacturing the circuit board of the first embodiment. [Diagram 5] FIG. 5 is a cross-sectional view that typically shows a state in which a core substrate and a resin sheet are laminated in the method for manufacturing a circuit board according to the first embodiment. [Figure 6] FIG. 6 is a schematic cross-sectional view for illustrating step (2) of the method for producing the circuit board according to the first embodiment. [Figure 7] FIG. 7 is a schematic cross-sectional view for explaining step (3) of the method for producing the circuit board according to the first embodiment. [Figure 8] FIG. 8 is a schematic cross-sectional view for explaining step (5) of the method for producing the circuit board according to the first embodiment. [Figure 9] FIG. 9 is a schematic cross-sectional view for explaining step (5) of the method for producing the circuit board according to the first embodiment. [Figure 10] FIG. 10 is a schematic cross-sectional view illustrating step (A) of the method for producing a circuit board according to the second embodiment. [Figure 11] FIG. 11 is a schematic cross-sectional view illustrating step (A) of the method for producing a circuit board according to the second embodiment. [Figure 12] FIG. 12 is a schematic cross-sectional view for explaining step (B) of the method for producing a circuit board according to the second embodiment. [Figure 13] FIG. 13 is a schematic cross-sectional view for explaining step (D) of the method for producing a circuit board according to the second embodiment. [Figure 14] FIG. 14 is a schematic plan view of an inductor component including a circuit board obtained by the method for manufacturing a circuit board according to the second embodiment, viewed from one side in the thickness direction. [Figure 15]FIG. 15 is a schematic diagram showing a cut end surface of an inductor component including a circuit board obtained by the method for producing a circuit board according to the second embodiment, cut at the position indicated by the dashed dotted line II-II. [Figure 16] FIG. 16 is a schematic plan view illustrating the configuration of a first conductor layer in an inductor component including a circuit board obtained by the method for manufacturing a circuit board according to the second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Each drawing merely shows the shape, size, and arrangement of components in a schematic manner to the extent that the invention can be understood. The present invention is not limited by the following description, and each component can be modified as appropriate. In the drawings used in the following description, similar components are indicated by the same reference numerals, and duplicated descriptions may be omitted. Furthermore, the configuration according to the embodiment of the present invention is not necessarily manufactured or used according to the arrangement of the illustrated example.

[0013] [Resin sheet] The resin sheet of the present invention is a resin sheet having a support and a resin composition layer formed from a resin composition provided on the support, wherein the resin composition contains (A) a magnetic powder, (B) an epoxy resin, (C) a dispersant, (D) a curing agent, and (E) a thermoplastic resin, and the (C) component has a polyester skeleton represented by the following general formula (1). [ka] (In general formula (1), R each independently represents a hydrocarbon group having 2 to 10 carbon atoms, and n represents an integer of 2 to 1000.)

[0014] In the present invention, by adding the dispersant (C) to the resin composition, a cured product having high relative magnetic permeability and excellent mechanical strength can be obtained. In addition, the cured product can usually reduce magnetic loss. Each layer constituting the resin sheet will be described in detail below.

[0015] <Support> Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred, and films made of plastic materials being more preferred.

[0016] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"); polycarbonate (hereinafter sometimes abbreviated as "PC"); acrylic polymers such as polymethyl methacrylate (hereinafter sometimes abbreviated as "PMMA"); cyclic polyolefins; triacetyl cellulose (hereinafter sometimes abbreviated as "TAC"); polyether sulfide (hereinafter sometimes abbreviated as "PES"); polyether ketone; polyimide; and the like. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0017] When a metal foil is used as the support, examples of the metal foil include copper foil and aluminum foil. Among them, copper foil is preferable. As the copper foil, a foil made of a single metal of copper may be used, or a foil made of an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.

[0018] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, an antistatic treatment or the like.

[0019] In addition, the support may be a support with a release layer having a release layer on the surface to be bonded to the resin composition layer. Examples of the release agent used in the release layer of the support with a release layer include one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. Examples of commercially available release agents include alkyd resin-based release agents such as "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation. Examples of the support with a release layer include "Lumirror T60" manufactured by Toray Industries, Inc.; "Purex" manufactured by Teijin Limited; and "Unipeel" manufactured by Unitika Limited.

[0020] The thickness of the support is preferably in the range of 5 μm to 75 μm, more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, the total thickness of the support with a release layer is preferably in the above range.

[0021] <Resin composition layer> In the resin sheet of the present invention, the resin composition layer provided on the support is formed from a resin composition, and the resin composition contains (A) a magnetic powder, (B) an epoxy resin, (C) a dispersant, (D) a curing agent, and (E) a thermoplastic resin, and the (C) component has a polyester skeleton represented by the following general formula (1). [ka] (In general formula (1), R each independently represents a hydrocarbon group having 2 to 10 carbon atoms, and n represents an integer of 2 to 1000.)

[0022] The resin composition may further contain optional components in combination with the components (A) to (E). The optional components include, for example, (F) other additives and (G) solvents. Each component contained in the resin composition will be described in detail below.

[0023] -(A)Magnetic powder- The resin composition contains (A) magnetic powder as component (A). As the (A) magnetic powder, particles of a material having a relative magnetic permeability greater than 1 can be used. The material of the (A) magnetic powder is usually an inorganic material, and may be a soft magnetic material or a hard magnetic material. The (A) magnetic powder may be used alone or in combination of two or more types. Thus, the (A) magnetic powder may be a soft magnetic powder, a hard magnetic powder, or a combination of a soft magnetic powder and a hard magnetic powder.

[0024] (A) Examples of magnetic powders include pure iron powder; Mg-Zn ferrite, Fe-Mn ferrite, Mn-Zn ferrite, Mn-Mg ferrite, Cu-Zn ferrite, Mg-Mn-Sr ferrite, Ni-Zn ferrite, Ba-Zn ferrite, Ba-Mg ferrite, Ba-Ni ferrite, Ba-Co ferrite, Ba-Ni-Co ferrite, Y ferrite, iron oxide powder (III), and triiron tetroxide. iron oxide powder; iron alloy metal powders such as Fe-Si alloy powder, Fe-Si-Al alloy powder, Fe-Cr alloy powder, Fe-Cr-Si alloy powder, Fe-Ni-Cr alloy powder, Fe-Cr-Al alloy powder, Fe-Ni alloy powder, Fe-Ni-Mo alloy powder, Fe-Ni-Mo-Cu alloy powder, Fe-Co alloy powder, or Fe-Ni-Co alloy powder; and amorphous alloys such as Co-based amorphous alloys.

[0025] Among them, the magnetic powder (A) is preferably at least one selected from iron oxide powder and iron alloy metal powder. The iron oxide powder preferably contains ferrite containing at least one selected from Ni, Cu, Mn, and Zn, and more preferably contains ferrite containing either Mn or Zn. The iron alloy metal powder preferably contains iron alloy metal powder containing at least one selected from Si, Cr, Al, Ni, and Co, and more preferably contains iron alloy metal powder containing Ni.

[0026] As the (A) magnetic powder, commercially available magnetic powders can be used. Specific examples of commercially available magnetic powders that can be used include "M03S", "M05S", "MZ03S", and "M001" manufactured by Powdertech Co., Ltd.; "MA-RCO-24" manufactured by Dowa Electronics Co., Ltd.; "PST-S" manufactured by Sanyo Special Steel Co., Ltd.; "AW2-08", "AW2-08PF20F", "AW2-08PF10F", "AW2-08PF3F", "Fe-3.5Si-4.5CrPF20F", "Fe-50NiPF20F", and "Fe-80Ni-4MoPF20F" manufactured by Epson Atmix Corporation; and "LD-M", "LD-MH", "KNI-106", and "KNI-106G" manufactured by JFE Chemical Corporation. SM", "KNI-106GS", "KNI-109", "KNI-109GSM", "KNI-109GS" manufactured by Toda Kogyo Co., Ltd.; "KNS-415", "BSF-547", "BSF-029", "BSN-125", "BSN-125", "BSN-714", "BSN-828", "S-1281", "S-1641", "S-1651", "S-1470", "S-1511", "S-2430" manufactured by Japan Metals and Chemical Industries Co., Ltd.; "JR09P2" manufactured by CIK Nanotech Co., Ltd.; "Nanotek" manufactured by Kinsei Matec Co., Ltd.; "JEMK-S" and "JEMK-H" manufactured by Kinsei Matec Co., Ltd.; and "Yttrium iron oxide" manufactured by ALDRICH. The (A) magnetic powder may be used alone, but from the viewpoint of obtaining the effects of the present invention more prominently, it is preferable to use two or more types in combination.

[0027] (A) The magnetic powder is preferably spherical. The aspect ratio (the value obtained by dividing the length of the long axis of the magnetic powder by the length of the short axis) is preferably 2 or less, more preferably 1.5 or less, and even more preferably 1.2 or less. In general, it is easier to improve the relative magnetic permeability when the magnetic powder is flat rather than spherical. However, it is usually preferable to use spherical magnetic powder, from the viewpoint of reducing magnetic loss.

[0028] From the viewpoint of improving the relative magnetic permeability, the average particle size of the (A) magnetic powder is preferably 0.01 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. Also, it is preferably 10 μm or less, more preferably 9 μm or less, and even more preferably 8 μm or less. When two or more kinds of (A) magnetic powders are used in combination, it is sufficient that the average particle size of the entire (A) component is within this range.

[0029] The average particle size of magnetic powder can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, a particle size distribution of magnetic powder is created on a volume basis using a laser diffraction / scattering type particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample is preferably magnetic powder dispersed in water using ultrasonic waves. Examples of laser diffraction / scattering type particle size distribution measuring devices that can be used include the "LA-500" manufactured by Horiba, Ltd. and the "SALD-2200" manufactured by Shimadzu Corporation.

[0030] (A) The specific surface area of ​​the magnetic powder is preferably 0.05 m from the viewpoint of improving the relative magnetic permeability. 2 / g or more, more preferably 0.1m 2 / g or more, more preferably 0.3m 2 / g or more. Also, preferably 10m 2 / g or less, more preferably 8m 2 / g or less, more preferably 5m 2 / g or less. The specific surface area of ​​the (A) magnetic powder can be measured by the BET method. When two or more types of (A) magnetic powder are used in combination, the specific surface area of ​​the (A) component as a whole should be within this range.

[0031] From the viewpoint of improving the relative magnetic permeability, the (A) magnetic powder preferably contains (A-1) magnetic powder having an average particle size of 1 μm or more, and (A-2) magnetic powder having an average particle size of less than 1 μm.

[0032] The average particle size of the magnetic powder (A-1) having an average particle size of 1 μm or more is 1 μm or more, preferably 1.2 μm or more, and more preferably 1.5 μm or more. The upper limit of the average particle size of the component (A-1) is preferably 10 μm or less, more preferably 9 μm or less, and even more preferably 8 μm or less. The average particle size of the component (A-1) can be measured by the method described above.

[0033] The specific surface area of ​​the component (A-1) is preferably 0.01 m 2 / g or more, more preferably 0.05m 2 / g or more, more preferably 0.1m 2 / g or more. Also, preferably 2m 2 / g or less, more preferably 1.5m 2 / g or less, more preferably 1m 2 The specific surface area of ​​the component (A-1) can be measured by the method described above.

[0034] The average particle size of the magnetic powder (A-2) having an average particle size of less than 1 μm is less than 1 μm, preferably 0.8 μm or less, more preferably 0.5 μm or less. The lower limit of the average particle size of the component (A-2) is preferably 0.005 μm or more, more preferably 0.01 μm or more, and even more preferably 0.02 μm or more. The average particle size of the component (A-2) can be measured by the method described above.

[0035] The specific surface area of ​​the component (A-2) is preferably 1 m 2 / g or more, more preferably 2m 2 / g or more, more preferably 3m 2 / g or more. Also, it is preferably 500m 2 / g or less, more preferably 400m 2 / g or less, more preferably 300m 2 The specific surface area of ​​the component (A-2) can be measured by the method described above.

[0036] Preferred embodiments of component (A) include (A-1) magnetic powder having an average particle size of 1 μm or more and 10 μm or less, and (A-2) magnetic powder having an average particle size of 0.005 μm or more and less than 1 μm, more preferably (A-1) magnetic powder having an average particle size of 1.2 μm or more and 9 μm or less, and (A-2) magnetic powder having an average particle size of 0.01 μm or more and less than 0.8 μm, and even more preferably (A-1) magnetic powder having an average particle size of 1.5 μm or more and 8 μm or less, and (A-2) magnetic powder having an average particle size of 0.02 μm or more and less than 0.5 μm.

[0037] From the viewpoint of improving the relative magnetic permeability and reducing the loss factor, the content (volume %) of the (A) magnetic powder is preferably 40% by volume or more, more preferably 50% by volume or more, and even more preferably 60% by volume or more, based on 100% by volume of the non-volatile components in the resin composition, and is preferably 85% by volume or less, more preferably 80% by volume or less, and even more preferably 70% by volume or less.

[0038] From the viewpoint of improving the relative magnetic permeability and reducing the loss factor, the content (mass%) of the (A) magnetic powder is preferably 70 mass% or more, more preferably 75 mass% or more, even more preferably 80 mass% or more, or 90 mass% or more, when the non-volatile components in the resin composition are taken as 100 mass%, and is preferably 98 mass% or less, more preferably 97 mass% or less, even more preferably 96 mass% or less, or 95 mass% or less. In the present invention, the content of each component in the resin composition is a value when the non-volatile components in the resin composition are taken as 100 mass %, unless otherwise specified.

[0039] When the (A) component includes the (A-1) component and the (A-2) component, the content (mass%) of the (A-1) component is preferably 50 mass% or more, more preferably 60 mass% or more, and even more preferably 70 mass% or more, based on 100 mass% of the non-volatile components in the resin composition, from the viewpoint of improving the relative permeability and reducing the loss factor. Also, it is preferably 90 mass% or less, more preferably 85 mass% or less, and even more preferably 80 mass% or less.

[0040] When the (A) component contains the (A-1) component and the (A-2) component, the content (mass%) of the (A-2) component is preferably 10 mass% or more, more preferably 15 mass% or more, and even more preferably 20 mass% or more, based on 100 mass% of the non-volatile components in the resin composition, from the viewpoint of improving the relative permeability and reducing the loss factor. Also, it is preferably 50 mass% or less, more preferably 40 mass% or less, and even more preferably 30 mass% or less.

[0041] When the content of the (A-1) component when the nonvolatile components in the resin composition are taken as 100% by mass is a1, and the content of the (A-2) component when the nonvolatile components in the resin composition are taken as 100% by mass is a2, a1 / a2 is preferably 10 or less, more preferably 8 or less, and even more preferably 5 or less, and is preferably 1 or more, more preferably 2 or more, and even more preferably 3 or more. By adjusting the content of the (A) component so that a1 / a2 falls within this range, it is possible to obtain the desired effects of the present invention more significantly.

[0042] -(B) Epoxy resin- The resin composition contains an epoxy resin (B) as the component (B). Examples of the epoxy resin (B) include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, naphthol novolac type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, and other epoxy resins having a condensed ring structure, glycidylamine type epoxy resin, glycidyl ester type epoxy resin, cresol novolac type epoxy resin, biphenyl type epoxy resin, linear aliphatic epoxy resin, butadiene type epoxy resin, alicyclic epoxy resin, heterocyclic epoxy resin, spiro ring-containing epoxy resin, cyclohexane dimethanol type epoxy resin, trimethylol type epoxy resin, tetraphenylethane type epoxy resin, and cyclic aliphatic diglycidyl ether type epoxy resin. The epoxy resin may be used alone or in combination of two or more. (B) The epoxy resin is preferably one or more selected from bisphenol A type epoxy resins and bisphenol F type epoxy resins, and more preferably contains bisphenol A type epoxy resins and bisphenol F type epoxy resins.

[0043] The (B) epoxy resin preferably contains an epoxy resin having two or more epoxy groups in one molecule. The (B) epoxy resin preferably has an aromatic structure, and when two or more epoxy resins are used, it is more preferable that at least one of them has an aromatic structure. The aromatic structure is a chemical structure generally defined as aromatic, and includes polycyclic aromatic rings and aromatic heterocycles. The proportion of the epoxy resin having two or more epoxy groups in one molecule relative to 100% by mass of the non-volatile components of the epoxy resin is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.

[0044] Epoxy resins include epoxy resins that are liquid at a temperature of 25° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 25° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition may contain only a liquid epoxy resin as the (B) epoxy resin, may contain only a solid epoxy resin, or may contain a combination of a liquid epoxy resin and a solid epoxy resin, but from the viewpoint of reducing the viscosity of the resin composition, it is preferable to contain only a liquid epoxy resin.

[0045] As the liquid epoxy resin, glycirol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane dimethanol type epoxy resin, cyclic aliphatic diglycidyl ether type epoxy resin, cyclic aliphatic glycidyl ether type epoxy resin, cyclic aliphatic glycidyl ether type epoxy resin and epoxy resin having a butadiene structure are preferred, and bisphenol A type epoxy resin and bisphenol F type epoxy resin are more preferred. Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL" (bisphenol A type epoxy resin), "jER807" (bisphenol F type epoxy resin), and "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630" and "630LSD" manufactured by Mitsubishi Chemical Corporation; "ED-523T" (glycirol type epoxy resin (ADEKA glycirol)), "EP-3980S" (glycidylamine type epoxy resin), and "EP-4088S" ( dicyclopentadiene type epoxy resins); "ZX1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin), "EX-201" (alicyclic glycidyl ether type epoxy resin), "ZX1658", "ZX1658GS" (alicyclic diglycidyl ether type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX Corporation; "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton) and "PB-3600" (epoxy resin having a butadiene structure) manufactured by Daicel Corporation. These may be used alone or in combination of two or more types.

[0046] As the solid epoxy resin, naphthalene-type tetrafunctional epoxy resin, cresol novolac-type epoxy resin, dicyclopentadiene-type epoxy resin, trisphenol-type epoxy resin, naphthol-type epoxy resin, biphenyl-type epoxy resin, naphthylene ether-type epoxy resin, anthracene-type epoxy resin, bisphenol A-type epoxy resin, and tetraphenylethane-type epoxy resin are preferable. Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin), "HP-4700", "HP-4710" (naphthalene type tetrafunctional epoxy resin), "N-690" (cresol novolac type epoxy resin), "N-695" (cresol novolac type epoxy resin), "HP-7200", "HP-7200HH", "HP-7200H" (dicyclopentadiene type epoxy resin), "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin), and "EPPN-502H" (trisphenol type epoxy resin), "NC7000L" (naphthol novolac type epoxy resin), "NC3000H", "NC3000L" (naphthol novolac type epoxy resin), manufactured by DIC Corporation. 00, "NC3000L", "NC3100" (biphenyl type epoxy resin); "ESN475V" (naphthalene type epoxy resin) and "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YL6121" (biphenyl type epoxy resin), "YX4000HK" (bixylenol type epoxy resin), "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "PG-100", "CG-500" manufactured by Osaka Gas Chemical Co., Ltd., "YL7760" (bisphenol AF type epoxy resin), "YL7800" (fluorene type epoxy resin), "jER1010" (solid bisphenol A type epoxy resin), "jER1031S" (tetraphenylethane type epoxy resin), etc. may be mentioned. These may be used alone or in combination of two or more types.

[0047] When a liquid epoxy resin and a solid epoxy resin are used in combination as the (B) epoxy resin, the ratio of the amounts thereof (liquid epoxy resin:solid epoxy resin) is preferably in the range of 1:0.1 to 1:4 by mass. By setting the ratio of the amount of the liquid epoxy resin to the solid epoxy resin in this range, effects such as a cured product having sufficient breaking strength can be obtained. From the viewpoint of the above effects, the ratio of the amount of the liquid epoxy resin to the solid epoxy resin (liquid epoxy resin:solid epoxy resin) is more preferably in the range of 1:0.3 to 1:3.5 by mass, further preferably in the range of 1:0.6 to 1:3, and particularly preferably in the range of 1:0.8 to 1:2.5.

[0048] From the viewpoint of obtaining a magnetic layer exhibiting good mechanical strength, the content of the (B) epoxy resin is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, even more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, when the non-volatile components in the resin composition are taken as 100% by mass. The upper limit of the content of the epoxy resin is not particularly limited as long as the effects of the present invention are achieved, but is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 2% by mass or less.

[0049] The content (volume %) of the (B) epoxy resin is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, when the non-volatile components in the resin composition are taken as 100% by volume. The upper limit is not particularly limited as long as the effects of the present invention are achieved, but is preferably 25% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less.

[0050] The epoxy equivalent of the (B) epoxy resin is preferably 50 g / eq. to 5000 g / eq., more preferably 50 g / eq. to 3000 g / eq., even more preferably 80 g / eq. to 2000 g / eq., and even more preferably 110 g / eq. to 1000 g / eq. Within this range, the crosslink density of the cured product is sufficient, and a magnetic layer with small surface roughness can be obtained. The epoxy equivalent can be measured according to JIS K7236, and is the mass of a resin containing one equivalent of epoxy groups.

[0051] The weight average molecular weight of the epoxy resin (B) is preferably 100 to 5000, more preferably 250 to 3000, and further preferably 400 to 1500. Here, the weight average molecular weight of the epoxy resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).

[0052] -(C) Dispersant- The resin composition contains, as component (C), a dispersant having a polyester skeleton represented by the following general formula (1). [ka] (In general formula (1), R each independently represents a divalent hydrocarbon group having 2 to 10 carbon atoms, and n represents an integer of 2 to 1000.)

[0053] As described above, if the content of the magnetic powder (A) is increased in order to improve the relative magnetic permeability, the mechanical strength of the cured product of the resin composition layer is reduced. In the present invention, the resin composition contains the component (C) as a dispersant, so that it is possible to improve the relative magnetic permeability and the mechanical strength at the same time, compared to a resin composition that does not contain the component (C) (i.e., a resin composition that has the same composition as the resin composition except that it does not contain the component (C)).

[0054] The component (C) has a polyester skeleton represented by general formula (1). [ka] (In general formula (1), R each independently represents a divalent hydrocarbon group having 2 to 10 carbon atoms, and n represents an integer of 2 to 1000.)

[0055] R in the general formula (1) represents a divalent hydrocarbon group having 2 to 10 carbon atoms. The hydrocarbon group has 2 or more carbon atoms, preferably 3 or more, more preferably 4 or more. The upper limit of the number of carbon atoms is 10 or less, preferably 8 or less, more preferably 6 or less. The hydrocarbon group may be linear, branched, or cyclic, and linear or branched hydrocarbon groups are preferred. Examples of the hydrocarbon group include an aliphatic hydrocarbon group and an aromatic hydrocarbon group, and an aliphatic hydrocarbon group is preferred. Examples of the hydrocarbon group include a saturated hydrocarbon group and an unsaturated hydrocarbon group, and a saturated hydrocarbon group is preferred. Specific examples of the hydrocarbon group include an alkylene group, an alkenylene group, an alkynylene group, and an arylene group. Among them, an alkylene group is particularly preferred as the hydrocarbon group from the viewpoint of obtaining the effects of the present invention remarkably.

[0056] Examples of the alkylene group include an ethylene group, a propylene group, a butylene group, a pentylene group, a hexylene group, a heptylene group, an octylene group, a nonylene group, and a decylene group. Examples of the alkenylene group include an ethenylene group, a propenylene group, a butenylene group, a pentenylene group, a hexenylene group, a heptenylene group, an octenylene group, a nonenylene group, and a decenylene group. Examples of the alkynylene group include an ethynylene group, a propenylene group, a butynylene group, a pentynylene group, a hexynylene group, a heptynylene group, an octynylene group, a nonenylene group, and a decynylene group. Examples of the arylene group include a phenylene group, a naphthylene group, and the like. Among these, a butylene group and a pentylene group are preferable as R.

[0057] The divalent hydrocarbon group represented by R in the general formula (1) may or may not have a substituent. The substituent is not particularly limited, and examples thereof include a halogen atom, -OH, -OC 1-6 Alkyl group, -N(C 1-10 Alkyl group) 2, C1-10 An alkyl group, C 6-10 An aryl group, -NH2, -CN, -C(O)O-C 1-10 An alkyl group, -COOH, -C(O)H, -NO2, etc. are exemplified. Here, the term "C p-q "(p and q are positive integers and satisfy p < q.) represents that the number of carbon atoms of the organic group described immediately after this term is p to q. For example, the expression "C 1-10 An alkyl group" indicates an alkyl group having 1 to 10 carbon atoms. These substituents may be bonded to each other to form a ring, and the ring structure includes a spiro ring and a fused ring.

[0058] The above-mentioned substituents may further have a substituent (hereinafter sometimes referred to as a "secondary substituent"). As the secondary substituent, the same ones as the above-mentioned substituents may be used unless otherwise specified.

[0059] In the general formula (1), n represents an integer of 2 to 1000. n is 2 or more, preferably 5 or more, more preferably 10 or more. The upper limit is 1000 or less, preferably 500 or less, more preferably 100 or less, 50 or less.

[0060] (C) component may contain an arbitrary skeleton in addition to the polyester skeleton represented by the general formula (1) as long as it does not inhibit the effects of the present invention. Examples of the arbitrary skeleton include a polyester skeleton in which R in the general formula (1) is a divalent hydrocarbon group having 1 or 11 or more carbon atoms (n is the same as in the formula (1)), and a polyallylamine skeleton. For example, the terminal of the polyester skeleton is not particularly limited.

[0061] Examples of the terminal of the (C) component include a residue of a carboxylic acid, a hydroxy group, a hydrogen atom, etc. described later.

[0062] The (C) component having a polyester skeleton represented by the general formula (1) can be produced, for example, by reacting a lactone and a carboxylic acid represented by the general formula (2).

Chemical formula

[0063] Examples of lactones represented by the general formula (2) include ε-caprolactone, β-propiolactone, γ-butyrolactone, δ-valerolactone, β-methyl-δ-valerolactone, 4-methylcaprolactone, and 2-methylcaprolactone.

[0064] The carboxylic acid may be one that functions as an initiator for ring-opening polymerization of lactone represented by general formula (2). Examples of such carboxylic acids include hydroxycarboxylic acids such as ricinoleic acid, ricinoleic acid, 9- and 10-hydroxystearic acid, castor oil fatty acid, hydrogenated castor oil fatty acid, lactic acid, 12-hydroxystearic acid, and glycolic acid; dodecanoic acid, and stearic acid. Among these, hydroxycarboxylic acids are preferred from the viewpoint of obtaining the effects of the present invention more significantly.

[0065] The reaction temperature is preferably 120 to 220° C., more preferably 160 to 210° C. The reaction time is preferably 0.5 to 72 hours. When the reaction is carried out under a nitrogen stream, a polyester having a high degree of polymerization can be obtained.

[0066] In addition, the above reaction may be carried out using a polymerization catalyst or a polymerization initiator, if necessary, in order to control the reaction.

[0067] Examples of the polymerization catalyst include quaternary ammonium salts such as tetramethylammonium chloride, tetrabutylammonium chloride, tetramethylammonium bromide, tetrabutylammonium bromide, tetramethylammonium iodide, tetrabutylammonium iodide, benzyltrimethylammonium chloride, benzyltrimethylammonium bromide, and benzyltrimethylammonium iodide; tetramethylphosphonium chloride, tetrabutylphosphonium chloride, tetramethylphosphonium bromide, tetrabutylphosphonium bromide, tetramethylphosphonium iodide, tetrabutylphosphonium iodide, and benzyltrimethylammonium iodide; quaternary phosphonium salts such as methylphosphonium chloride, benzyltrimethylphosphonium bromide, benzyltrimethylphosphonium iodide, tetraphenylphosphonium chloride, tetraphenylphosphonium bromide, and tetraphenylphosphonium iodine; phosphorus compounds such as triphenylphosphine; organic carboxylates such as potassium acetate, sodium acetate, potassium benzoate, and sodium benzoate; alkali metal alcoholates such as sodium alcoholate and potassium alcoholate; tertiary amines; organic tin compounds; organic aluminum compounds; organic titanate compounds such as tetrabutyl titanate; and zinc compounds such as zinc chloride.

[0068] Examples of the polymerization initiator include aliphatic monocarboxylic acids such as acetic acid, propionic acid, caprylic acid, nonanoic acid, capric acid, octylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, isononanoic acid, and arachic acid; and aromatic monocarboxylic acids such as benzoic acid and p-butylbenzoic acid.

[0069] In the production of the component (C), in addition to the lactone and carboxylic acid represented by the general formula (2), any other monomer may be used as long as it does not impair the effects of the present invention. Examples of the optional monomer include polyallylamine. For example, when polyallylamine is used as the optional monomer, the component (C) containing a polyallylamine skeleton in addition to the polyester skeleton represented by the general formula (1) can be produced. The reaction temperature and reaction time are the same as those in the production of the component (C) having the polyester skeleton represented by the general formula (1).

[0070] Polyallylamine can be obtained by polymerizing allylamine in the presence of a polymerization initiator and / or a chain transfer catalyst.

[0071] The polymerization initiator is not particularly limited, and examples thereof include ketone peroxides such as methyl ethyl ketone, diacyl peroxides such as benzoyl peroxide, peroxydicarbonates such as diisopropyl peroxydicarbonate, peroxyketals such as 1,1-bis(t-butylperoxy)cyclohexane, hydroperoxides such as t-butyl hydroperoxide, peroxyesters such as t-butyl peroxypivalate, and other azobisisoptylonitrile, hydrogen peroxide, and ferrous salts. Furthermore, the polymerization initiators described in JP-B-2-14364 may be used. These may be used alone or in combination of two or more.

[0072] The chain transfer catalyst is not particularly limited, and examples thereof include alkyl mercaptans such as lauryl mercaptan, thiocarboxylic acids such as mercaptoacetic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, and thiocarboxylic acid esters such as butyl thioglycolate, 2-ethylhexyl thioglycolate, etc. These may be used alone or in combination of two or more.

[0073] The weight-average molecular weight of the polyallylamine is preferably 150 to 100,000, more preferably 600 to 20,000. When the weight-average molecular weight is 150 or more, the adsorption force to particles of the component (A) etc. is improved, and particle dispersibility is improved, and when the weight-average molecular weight is 100,000 or less, aggregation between particles can be suppressed, and particle dispersibility is improved. Note that polyallylamine with any weight-average molecular weight may be produced using the method described in JP-B-2-14364.

[0074] Commercially available polyallylamine products can be used. Examples of commercially available polyallylamine products include "PAA-01", "PAA-03", "PAA-05", "PAA-08", "PAA-15", "PAA-15C", and "PAA-25" manufactured by Nittobo Medical Co., Ltd.

[0075] The pH of component (C) can usually be 4 or more and less than 7. The pH can be measured by an indicator method. Specifically, the pH can be measured by immersing a measurement sample (22°C) with a dispersant concentration of 0.1 g / mL, which is prepared by dissolving the dispersant in acetone, into a pH test paper. As the pH test paper, a pH test paper capable of measuring pH in the acidic range (e.g., a measurement range of pH 0.0 to 14.0, pH 1.0 to 14.0, or pH 0.5 to 5.0, etc.) can be used, such as the pH test paper "pH test paper pH 1 to 14" (pH measurement range pH 1.0 to 14.0) manufactured by AS ONE Corporation.

[0076] From the viewpoint of obtaining the effects of the present invention remarkably, the acid value of the component (C) is preferably 1 mgKOH / g or more, more preferably 3 mgKOH / g or more, even more preferably 5 mgKOH / g, and is preferably 30 mgKOH / g or less, more preferably 25 mgKOH / g or less, even more preferably 20 mgKOH / g or less. The acid value can be measured by neutralization titration.

[0077] When component (C) is a dispersant reacted with polyallylamine, the amine value is, from the viewpoint of obtaining the effects of the present invention significantly, preferably 1 mgKOH / g or more, more preferably 5 mgKOH / g or more, even more preferably 10 mgKOH / g or more, and preferably 45 mgKOH / g or less, more preferably 40 mgKOH / g or less, even more preferably 35 mgKOH / g or less. The amine value can be measured by neutralization titration.

[0078] From the viewpoint of obtaining the remarkable effects of the present invention, the weight average molecular weight of the component (C) is preferably at least 1000, more preferably at least 1500, and even more preferably at least 2000, and is preferably at most 50000, more preferably at most 40000, and even more preferably at most 30000. The weight average molecular weight is a polystyrene-equivalent weight molecular weight measured by gel permeation chromatography (GPC).

[0079] From the viewpoint of prominently exerting the effects of the present invention, the content of the (C) component is preferably 0.1 mass % or more, more preferably 0.2 mass % or more, and even more preferably 0.3 mass % or more, based on 100 mass % of the non-volatile components in the resin composition, and the upper limit is preferably 5 mass % or less, more preferably 3 mass % or less, and even more preferably 1 mass % or less.

[0080] When the mass of component (C) when the nonvolatile components in the resin composition are taken as 100% by mass is taken as C1, and the mass of magnetic powder (A) when the nonvolatile components in the resin composition are taken as 100% by mass is taken as A1, (C1 / A1) x 100 is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.3 or more, and is preferably 10 or less, more preferably 5 or less, and even more preferably 1 or less. By adjusting the masses of component (A) and (C) so that (C1 / A1) x 100 is within this range, it is possible to obtain the desired effects of the present invention more significantly.

[0081] -(D) Hardener- The resin composition contains a (D) curing agent as the (D) component. The (D) curing agent includes an epoxy resin curing agent having a function of curing the (B) epoxy resin, and a curing accelerator having a function of accelerating the curing rate of the (B) epoxy resin. The curing accelerator is usually used in combination with an epoxy resin curing agent. The resin composition preferably contains an epoxy resin curing agent as the (D) curing agent, and more preferably contains a curing accelerator together with the epoxy resin curing agent as the (D) curing agent.

[0082] (Epoxy resin hardener) The epoxy resin curing agent can usually react with the (B) epoxy resin to cure the resin composition. Examples of the epoxy resin curing agent include phenol-based epoxy resin curing agents, naphthol-based epoxy resin curing agents, active ester-based epoxy resin curing agents, acid anhydride-based epoxy resin curing agents, benzoxazine-based epoxy resin curing agents, cyanate ester-based epoxy resin curing agents, and imidazole-based epoxy resin curing agents. From the viewpoint of obtaining the effects of the present invention remarkably, the epoxy resin curing agent is preferably one or more selected from phenol-based epoxy resin curing agents and naphthol-based epoxy resin curing agents. The epoxy resin curing agent may be used alone or in combination of two or more.

[0083] As the phenol-based epoxy resin curing agent and naphthol-based epoxy resin curing agent, from the viewpoint of heat resistance and water resistance, a phenol-based epoxy resin curing agent having a novolac structure or a naphthol-based epoxy resin curing agent having a novolac structure is preferred. As the phenol-based epoxy resin curing agent, a nitrogen-containing phenol-based epoxy resin curing agent is preferred, a triazine skeleton-containing phenol-based epoxy resin curing agent is more preferred, and a triazine skeleton-containing phenol novolac epoxy resin curing agent is even more preferred.

[0084] Specific examples of phenol-based epoxy resin curing agents and naphthol-based epoxy resin curing agents include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd., "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd., "SN170", "SN180", "SN190", "SN475", "SN485", "SN495V", "SN375", and "SN395" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., "TD-2090", "LA-7052", "LA-7054", "LA-1356", "LA-3018-50P", "EXB-9500", "HPC-9500", "KA-1160", "KA-1163", and "KA-1165" manufactured by DIC Corporation, and "GDP-6115L" and "GDP-6115H" manufactured by Gun-ei Chemical Co., Ltd.

[0085] The active ester epoxy resin curing agent is not particularly limited, but generally, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, are preferably used. The active ester epoxy resin curing agent is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester epoxy resin curing agent obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester epoxy resin curing agent obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.

[0086] Specifically, active ester-based epoxy resin curing agents containing a dicyclopentadiene-type diphenol structure, active ester-based epoxy resin curing agents containing a naphthalene structure, active ester-based epoxy resin curing agents containing an acetylated product of phenol novolac, and active ester-based epoxy resin curing agents containing a benzoylated product of phenol novolac are preferred. The "dicyclopentadiene-type diphenol structure" refers to a divalent structure consisting of phenylene-dicyclopentylene-phenylene.

[0087] Commercially available active ester epoxy resin curing agents include DIC Corporation's "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "EXB-8000L-65TM" as active ester epoxy resin curing agents containing a dicyclopentadiene-type diphenol structure; DIC Corporation's "EXB9416-70BK" as an active ester compound containing a naphthalene structure; Mitsubishi Chemical Corporation's "DC808" as an active ester epoxy resin curing agent containing an acetylated product of phenol novolac; Mitsubishi Chemical Corporation's "YLH1026", "YLH1030", and "YLH1048" as active ester epoxy resin curing agents containing a benzoylated product of phenol novolac; and Mitsubishi Chemical Corporation's "DC808" as an active ester epoxy resin curing agent which is an acetylated product of phenol novolac.

[0088] Examples of the acid anhydride epoxy resin curing agent include an epoxy resin curing agent having one or more acid anhydride groups in one molecule. Specific examples of the acid anhydride epoxy resin curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarbo Examples of such anhydrides include carboxylic acid dianhydride, biphenyltetracarboxylic acid dianhydride, naphthalenetetracarboxylic acid dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic acid dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid.

[0089] Commercially available acid anhydride-based epoxy resin curing agents include "HNA-100" and "MH-700" manufactured by New Japan Chemical Co., Ltd.

[0090] Specific examples of benzoxazine-based epoxy resin curing agents include "HFB2006M" manufactured by Showa Polymer Co., Ltd., and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.

[0091] Examples of the cyanate ester-based epoxy resin curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based epoxy resin curing agents include "PT30" and "PT60" (both of which are phenol novolac-type multifunctional cyanate ester resins), "BA230" and "BA230S75" (prepolymers in which a portion or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan Ltd.

[0092] Examples of imidazole-based epoxy resin curing agents include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-phenylimidazo 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2- Examples of the imidazole compound include phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and other imidazole compounds and adducts of imidazole compounds with epoxy resins. Of these, 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole are preferred.

[0093] As the imidazole-based epoxy resin curing agent, a commercially available product may be used, for example, "2MZA-PW" and "2PHZ-PW" manufactured by Shikoku Chemical Industry Co., Ltd., and "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0094] The ratio of the amount of epoxy resin to the epoxy resin curing agent is preferably in the range of 1:0.2 to 1:2, more preferably in the range of 1:0.3 to 1:1.5, and even more preferably in the range of 1:0.4 to 1:1. Here, the reactive group of the epoxy resin curing agent is an active hydroxyl group, an active ester group, etc., and varies depending on the type of the epoxy resin curing agent. The total number of epoxy groups of the epoxy resin is the value obtained by dividing the mass of the non-volatile component of each epoxy resin by the epoxy equivalent, and the total number of reactive groups of the epoxy resin curing agent is the value obtained by dividing the mass of the non-volatile component of each epoxy resin curing agent by the reactive group ...

[0095] From the viewpoint of significantly obtaining the effects of the present invention, the content of the epoxy resin curing agent is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, based on 100% by mass of the resin component in the resin composition, and the upper limit is preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less.

[0096] (Cure accelerator) The curing accelerator usually acts as a catalyst in the curing reaction of the epoxy resin (B) to accelerate the curing reaction. Examples of the curing accelerator include amine-based curing accelerators, imidazole-based curing accelerators, phosphorus-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators. From the viewpoint of reducing the viscosity of the resin composition, the curing accelerator is preferably an amine-based curing accelerator, an imidazole-based curing accelerator, or a guanidine-based curing accelerator, and more preferably an imidazole-based curing accelerator from the viewpoint of improving the mechanical strength of the cured product obtained. The curing accelerator may be used alone or in combination of two or more types. The curing accelerator is generally used in combination with an epoxy resin curing agent.

[0097] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene, with 4-dimethylaminopyridine and 1,8-diazabicyclo(5,4,0)-undecene being preferred.

[0098] As the amine-based curing accelerator, commercially available products may be used, for example, "PN-50", "PN-23", "MY-25" and the like manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0099] The imidazole-based curing accelerator is the same as the imidazole-based epoxy resin curing agent described above. When the imidazole-based epoxy resin curing agent is used in combination with other epoxy resin curing agents, it may function as a curing accelerator.

[0100] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, butyltriphenylphosphonium thiocyanate, and the like, with triphenylphosphine and tetrabutylphosphonium decanoate being preferred.

[0101] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, and 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene. Examples of such biguanide include o-[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide. Of these, dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene are preferred.

[0102] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0103] From the viewpoint of obtaining the effects of the present invention prominently, the content of the curing accelerator is preferably 0.001% by mass or more, more preferably 0.005% by mass or more, and even more preferably 0.01% by mass or more, based on 100% by mass of the resin component in the resin composition, and the upper limit is preferably 1% by mass or less, more preferably 0.1% by mass or less, and even more preferably 0.05% by mass or less.

[0104] From the viewpoint of significantly obtaining the effects of the present invention, the content of the (D) curing agent is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, based on 100% by mass of the non-volatile components in the resin composition, and the upper limit is preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less.

[0105] When the mass of the (D) curing agent when the nonvolatile components in the resin composition are 100% by mass is D1, and the mass of the (C) dispersant when the nonvolatile components in the resin composition are 100% by mass is C1, C1 / D1 is preferably 0.01 or more, more preferably 0.05 or more, and even more preferably 0.1 or more, and is preferably 5 or less, more preferably 1.5 or less, and even more preferably 1 or less. By adjusting the masses of the (C) component and (D) so that C1 / D1 is within this range, it is possible to obtain the desired effects of the present invention more significantly.

[0106] When the mass of the (A) magnetic powder is A1 when the nonvolatile components in the resin composition are 100% by mass, the mass of the (B) epoxy resin is B1 when the nonvolatile components in the resin composition are 100% by mass, the mass of the (C) dispersant is C1 when the nonvolatile components in the resin composition are 100% by mass, and the mass of the (D) curing agent is D1 when the nonvolatile components in the resin composition are 100% by mass, (B1+C1+D1) / A1 is preferably 0.001 or more, more preferably 0.005 or more, and even more preferably 0.01 or more, and is preferably 1 or less, more preferably 0.5 or less, and even more preferably 0.3 or less. By adjusting the masses of the (A) component to the (D) component so that (B1+C1+D1) / A1 is within this range, it is possible to obtain the desired effects of the present invention more significantly.

[0107] When the mass of the (A) magnetic powder when the nonvolatile components in the resin composition are 100% by mass is A1, the mass of the (C) dispersant when the nonvolatile components in the resin composition are 100% by mass is C1, and the mass of the (D) curing agent when the nonvolatile components in the resin composition are 100% by mass is D1, ((C1+D1) / A1)×100 is preferably 0.1 or more, more preferably 0.5 or more, and even more preferably 1 or more, and is preferably 10 or less, more preferably 5 or less, and even more preferably 3 or less. By adjusting the masses of the (A), (C) and (D) components so that ((C1+D1) / A1)×100 is within this range, it is possible to obtain the desired effects of the present invention more significantly.

[0108] -(E) Thermoplastic resin- The resin composition contains a thermoplastic resin (E) as component (E). By containing component (E) in the resin composition, the stress of the cured product of the resin composition layer is alleviated, and the mechanical strength of the cured product can be improved.

[0109] Examples of the (E) thermoplastic resin include phenoxy resin, polyvinyl acetal resin, polyolefin resin, polyimide resin, polybutadiene resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polyetheretherketone resin, polyester resin, etc., and phenoxy resin is preferred. (E) Thermoplastic resin may be used alone or in combination of two or more.

[0110] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group. Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.; "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", "YL7482", and "YL7891BH30" manufactured by Mitsubishi Chemical Corporation.

[0111] Examples of polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred.Specific examples of polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd.; S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.

[0112] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.

[0113] Specific examples of polyimide resins include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd. Specific examples of polyimide resins also include modified polyimides such as linear polyimides obtained by reacting bifunctional hydroxyl-terminated polybutadiene, a diisocyanate compound, and a tetrabasic acid anhydride (polyimides described in JP-A-2006-37083), and polysiloxane skeleton-containing polyimides (polyimides described in JP-A-2002-12667 and JP-A-2000-319386, etc.).

[0114] Examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxy group-containing polybutadiene resins, phenolic hydroxy group-containing polybutadiene resins, carboxy group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, urethane group-containing polybutadiene resins, polyphenylene ether-polybutadiene resins, and the like.

[0115] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.

[0116] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.

[0117] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.

[0118] A specific example of the polyphenylene ether resin is NORYL SA90 manufactured by SABIC, etc. A specific example of the polyetherimide resin is ULTEM manufactured by GE, etc.

[0119] Examples of polycarbonate resins include hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, and urethane group-containing carbonate resins. Specific examples of polycarbonate resins include "FPC0220" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002" and "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diol) manufactured by Kuraray Co., Ltd. Specific examples of polyether ether ketone resins include "Sumiploy K" manufactured by Sumitomo Chemical Co., Ltd.

[0120] Examples of polyester resins include polyethylene terephthalate resins, polyethylene naphthalate resins, polybutylene terephthalate resins, polybutylene naphthalate resins, polytrimethylene terephthalate resins, polytrimethylene naphthalate resins, and polycyclohexane dimethyl terephthalate resins.

[0121] The weight average molecular weight (Mw) of the (E) thermoplastic resin is preferably greater than 5,000, more preferably 8,000 or more, even more preferably 10,000 or more, and particularly preferably 20,000 or more. There is no particular upper limit, and it may be, for example, 1 million or less, 500,000 or less, or 100,000 or less. The polystyrene-equivalent weight average molecular weight of the (E) thermoplastic resin is measured by gel permeation chromatography (GPC). Specifically, the polystyrene-equivalent weight average molecular weight of the (E) thermoplastic resin is measured at a column temperature of 40° C. using a measuring device LC-9A / RID-6A manufactured by Shimadzu Corporation, a column Shodex K-800P / K-804L / K-804L manufactured by Showa Denko K.K., chloroform or the like as a mobile phase, and can be calculated using a calibration curve of standard polystyrene.

[0122] The content of the (E) thermoplastic resin is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, particularly preferably 0.3% by mass or more, and is preferably 5% by mass or less, more preferably 3% by mass or less, particularly preferably 2% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the (E) thermoplastic resin is within the above range, the magnetic properties of the cured product of the resin composition can be particularly good.

[0123] When the mass of the (E) thermoplastic resin when the nonvolatile components in the resin composition are taken as 100% by mass is taken as E1, and the mass of the (B) epoxy resin when the nonvolatile components in the resin composition are taken as 100% by mass is taken as B1, B1 / E1 is preferably 0.1 or more, more preferably 0.3 or more, and even more preferably 0.5 or more, and is preferably 5 or less, more preferably 1.5 or less, and even more preferably 1 or less. By adjusting the masses of the (B) component and (E) so that B1 / E1 is within this range, it is possible to obtain the desired effects of the present invention more significantly.

[0124] When the mass of the (E) thermoplastic resin when the nonvolatile components in the resin composition are taken as 100% by mass is taken as E1, and the mass of the (C) dispersant when the nonvolatile components in the resin composition are taken as 100% by mass is taken as C1, C1 / E1 is preferably 0.01 or more, more preferably 0.05 or more, even more preferably 0.1 or more, and is preferably 5 or less, more preferably 1.5 or less, and even more preferably 1 or less. By adjusting the masses of the (C) component and (E) so that C1 / E1 is within this range, it is possible to obtain the desired effects of the present invention more significantly.

[0125] When the mass of the (A) magnetic powder is A1 when the nonvolatile components in the resin composition are 100% by mass, the mass of the (B) epoxy resin is B1 when the nonvolatile components in the resin composition are 100% by mass, the mass of the (C) dispersant is C1 when the nonvolatile components in the resin composition are 100% by mass, the mass of the (D) curing agent is D1 when the nonvolatile components in the resin composition are 100% by mass, and the mass of the (E) thermoplastic resin is E1 when the nonvolatile components in the resin composition are 100% by mass, (B1+C1+D1+E1) / A1 is preferably 0.001 or more, more preferably 0.01 or more, and even more preferably 0.05 or more, and is preferably 1 or less, more preferably 0.5 or less, and even more preferably 0.3 or less. By adjusting the masses of the (A) component to the (E) component so that (B1+C1+D1) / A1 is within this range, it is possible to obtain the desired effects of the present invention more significantly.

[0126] When the mass of the (A) magnetic powder when the nonvolatile components in the resin composition are 100% by mass is A1, the mass of the (C) dispersant when the nonvolatile components in the resin composition are 100% by mass is C1, and the mass of the (E) thermoplastic resin when the nonvolatile components in the resin composition are 100% by mass is E1, ((C1+E1) / A1)×100 is preferably 0.1 or more, more preferably 0.5 or more, and even more preferably 1 or more, and is preferably 10 or less, more preferably 5 or less, and even more preferably 3 or less. By adjusting the masses of the (A), (C) and (E) components so that ((C1+E1) / A1)×100 is within the above range, it is possible to obtain the desired effects of the present invention more significantly.

[0127] -(F) Other additives- The resin composition may further contain other additives (F) as necessary. Examples of such other additives include curing retarders such as triethyl borate, inorganic fillers (excluding those corresponding to magnetic powders), flame retardants, organic fillers, organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds, as well as resin additives such as thickeners, defoamers, leveling agents, adhesion promoters, and colorants.

[0128] -(G) Solvent- The resin composition may further contain a solvent (G) as a volatile component in addition to the non-volatile components (A) to (F) described above.

[0129] (G) As the solvent, an organic solvent is usually used. Examples of the organic solvent include ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, and diphenyl ether; alcohol-based solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, and methyl methoxypropionate. Examples of the solvent include ether ester solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butylcarbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. The (G) solvent may be used alone or in combination of two or more.

[0130] The amount of the (G) solvent is preferably set so that the melt viscosity of the resin composition or the resin composition layer containing the resin composition can be adjusted to an appropriate range. The resin composition may not contain the (G) solvent. For example, the content of the organic solvent contained in the above-mentioned resin composition is preferably less than 1.0 mass%, more preferably 0.8 mass% or less, even more preferably 0.5 mass% or less, and particularly preferably 0.1 mass% or less, based on the total mass of the resin composition. There is no particular limit to the lower limit, but it is 0.001 mass% or more, or no solvent is contained. By reducing the amount of the solvent in the resin composition, it is possible to suppress the generation of voids due to the evaporation of the solvent.

[0131] The thickness of the resin composition layer varies depending on the thickness of the wiring, the thickness of the core substrate, and the dimensions of the through-hole, but is preferably 5 μm or more, more preferably 10 μm or more, and particularly preferably 50 μm or more, and is preferably 600 μm or less, more preferably 300 μm or less, and particularly preferably 200 μm or less.

[0132] <Method of manufacturing resin sheet> The resin sheet can be produced, for example, by a method including coating a support with a resin composition. The resin composition layer can be produced, for example, by preparing a resin varnish in which the resin composition is dissolved or dispersed in a solvent, coating the resin varnish on a support using a die coater or the like, and then drying the resin varnish to form a resin composition layer. The resin sheet can also be produced by coating the resin composition directly on a support using a die coater or the like to form a resin composition layer. The above-mentioned (G) solvent can be used as the solvent.

[0133] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but drying is performed so that the content of organic solvent in the resin composition layer becomes 10 mass % or less, preferably 5 mass % or less. Although it varies depending on the boiling point of the organic solvent in the resin varnish, for example, when a resin varnish containing 30 mass % to 60 mass % of organic solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.

[0134] In the resin sheet, a protective film equivalent to the support can be further laminated on the surface of the resin composition layer not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to suppress adhesion of dirt and scratches on the surface of the resin composition layer. The resin sheet can be stored in a roll shape. When the resin sheet has a protective film, it can be used by peeling off the protective film.

[0135] <Physical properties of resin composition layer (resin composition)> The cured product obtained by heating the resin composition layer (resin composition) at 190°C for 90 minutes exhibits the property of excellent mechanical strength (tensile breaking strength). Thus, the cured product provides a magnetic layer with excellent tensile breaking strength. The tensile breaking strength is preferably 60 MPa or more, more preferably 70 MPa or more, and even more preferably 75 MPa or more. There is no particular upper limit, but it may be 150 MPa or less. The mechanical strength (tensile breaking strength) can be measured by the method described in the examples below.

[0136] A cured product obtained by heating a resin composition layer (resin composition) at 190°C for 90 minutes exhibits the characteristic of having a high relative magnetic permeability at a frequency of 50 MHz. Thus, the cured product provides a magnetic layer with a high relative magnetic permeability. The relative magnetic permeability of this cured product at a frequency of 50 MHz is preferably 20 or more, more preferably 20.5 or more, and even more preferably 21 or more. The upper limit is not particularly limited, but may be 100 or less. The relative magnetic permeability can be measured by the method described in the examples below.

[0137] A cured product obtained by heating a resin composition layer (resin composition) at 190°C for 90 minutes usually exhibits the property of low magnetic loss at a frequency of 50 MHz. Thus, the cured product provides a magnetic layer with low magnetic loss. The magnetic loss of this cured product at a frequency of 50 MHz is preferably 0.5 or less, more preferably 0.3 or less, and even more preferably 0.1 or less. The lower limit is not particularly limited, but may be 0.001 or more. The magnetic loss can be measured by the method described in the examples below.

[0138] From the viewpoint of utilizing the above-mentioned advantages, the resin sheet preferably uses a resin composition layer (resin composition) for forming a magnetic layer of a circuit board. Also, from the viewpoint of utilizing the above-mentioned advantages, the resin sheet preferably uses a resin composition layer (resin composition) for filling through-holes of a core substrate. When a core substrate and a resin sheet are laminated, a part or all of the resin composition layer can be inserted into the through-holes, and the through-holes can be filled with the resin composition. Then, the resin composition can be cured to form a magnetic layer in the through-holes.

[0139] [Resin composition] The resin composition of the present invention comprises (A) a magnetic powder, (B) an epoxy resin, (C) a dispersant, (D) a curing agent, and (E) a thermoplastic resin, wherein when the mass of the thermoplastic resin (E) is E1 when the nonvolatile components in the resin composition are 100 mass%, and the mass of the epoxy resin (B) is B1 when the nonvolatile components in the resin composition are 100 mass%, B1 / E1 is 0.1 or more and 5 or less, and the component (C) has a polyester skeleton represented by the following general formula (1). [ka] (In general formula (1), R each independently represents a hydrocarbon group having 2 to 10 carbon atoms, and n represents an integer of 2 to 1000.)

[0140] The resin composition may be the same composition as the resin composition layer described above, except that the resin composition may have a state other than the state of the resin composition layer formed on the sheet. Each component contained in the resin composition is as described above.

[0141] [Cured product] The cured product of the present invention is obtained by curing the resin composition layer of the present invention. The cured product of the present invention is obtained by curing the resin composition of the present invention. The curing conditions of the resin composition layer and the resin composition may be the conditions of step (2) described below. Furthermore, the resin composition layer and the resin composition may be preheated before being thermally cured, and the heating may be performed multiple times including the preheating.

[0142] [Circuit board and its manufacturing method] The circuit board according to one embodiment of the present invention includes a magnetic layer. This magnetic layer includes a cured product of the resin composition layer of the resin sheet described above, and preferably includes only the cured product of the resin composition described above. There is no limitation on the specific structure of the circuit board as long as it includes a magnetic layer including the cured product of the resin composition layer described above. The circuit board of the first embodiment is a circuit board including a core substrate as a substrate having a through hole formed therein, and a magnetic layer filled in the through hole. The circuit board of the second embodiment is a circuit board including a magnetic layer formed by the cured product of the resin composition layer of the resin sheet. In these circuit boards, the magnetic layer may be a layer obtained by curing the resin composition layer, or may be a layer obtained by curing the resin composition. Hereinafter, the first and second embodiments of the method for manufacturing the circuit board will be described. However, the method for manufacturing the circuit board according to the present invention is not limited to the first and second embodiments exemplified below.

[0143] First Embodiment The circuit board of the first embodiment includes a core substrate having a through hole formed therein, and a magnetic layer filled in the through hole. (1) laminating a core substrate having through holes formed therein and a resin sheet such that the through holes are filled with a resin composition layer; (2) curing the resin composition layer to form a magnetic layer; Includes, in this order.

[0144] The method for producing a circuit board according to the first embodiment may include any step in combination with the steps (1) and (2). For example, the method for producing a circuit board may include the following steps: (3) polishing the magnetic layer; (4) subjecting the magnetic layer to a roughening treatment; and (5) forming a conductor layer on the magnetic layer; Typically, steps (3), (4) and (5) are carried out in this order.

[0145] <Process (1)> Step (1) usually includes a step of preparing a core substrate having a through hole formed therein. The core substrate may be prepared by purchasing it from the market. Alternatively, the core substrate may be prepared by manufacturing it using an appropriate material. An example of a method for manufacturing the core substrate will be described below.

[0146] Fig. 1 is a cross-sectional view that shows a schematic diagram of a core substrate 10 before through holes are formed in the method for manufacturing a circuit board according to the first embodiment of the present invention. The step of preparing the core substrate 10 may include preparing a core substrate 10 in which no through holes to be filled with a magnetic layer are formed, as in the example shown in Fig. 1. This core substrate 10 is a substrate in which through holes are not formed, and may be a plate-shaped member.

[0147] The core substrate 10 usually includes a support substrate 11. Examples of the support substrate 11 include insulating substrates such as a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. A metal layer may be provided on the support substrate 11. The metal layer may be provided on one side or both sides of the support substrate 11. Here, an example is shown in which metal layers 12 and 13 are provided on both surfaces of the support substrate 11. Examples of the metal layers 12 and 13 include layers formed of a metal such as copper. The metal layers 12 and 13 may be, for example, copper foil such as a copper foil with a carrier, or may be metal layers formed of a material for the conductor layer described later.

[0148] FIG. 2 is a cross-sectional view showing a core substrate 10 having a through hole 14 formed therein in the method for manufacturing a circuit board according to the first embodiment of the present invention. The step of preparing the core substrate 10 may include forming the through hole 14 in the core substrate 10, as in the example shown in FIG. 2. The through hole 14 can be formed by, for example, drilling, laser irradiation, plasma irradiation, or the like. Usually, the through hole 14 can be formed by forming a through hole in the core substrate 10. As a specific example, the through hole 14 can be formed by using a commercially available drilling device. An example of a commercially available drilling device is the "ND-1S211" manufactured by Hitachi Via Mechanics.

[0149] FIG. 3 is a cross-sectional view showing a core substrate 10 having a plating layer 20 formed in a through hole 14 in the method for manufacturing a circuit board according to the first embodiment of the present invention. The step of preparing the core substrate 10 may include forming the plating layer 20 as shown in FIG. 3 after subjecting the core substrate 10 to a roughening treatment as necessary. The roughening treatment may be either a dry or wet roughening treatment. An example of the dry roughening treatment is a plasma treatment. An example of the wet roughening treatment is a method in which a swelling treatment using a swelling liquid, a roughening treatment using an oxidizing agent, and a neutralization treatment using a neutralizing liquid are performed in this order. The plating layer 20 may be formed by a plating method. The procedure for forming the plating layer 20 by a plating method may be the same as the formation of the conductor layer in step (5) described later. Here, an example is shown in which the plating layer 20 is formed in the through hole 14, on the surface of the metal layer 12, and on the surface of the metal layer 13. In addition, in this example, the core substrate provided with the plating layer 20 will be described by assigning the same reference numeral "10" as the core substrate 10 before the plating layer 20 is formed.

[0150] FIG. 4 is a cross-sectional view showing a schematic state of laminating a core substrate 10 and a resin sheet 30 in a manufacturing method of a circuit board according to the first embodiment of the present invention. Step (1) includes preparing a core substrate 10 having a through hole 14 formed therein, and then laminating the core substrate 10 and the resin sheet 30 as shown in FIG. 4. In this embodiment, an example is shown and described in which a resin sheet 30 including a resin composition layer 31 and a support 32 is laminated on one surface 10U of the core substrate 10. In the following description, the surface 10U of the core substrate 10 that is bonded to the resin sheet 30 may be referred to as the "first surface 10U", and the opposite surface may be referred to as the "second surface 10D".

[0151] The lamination of the core substrate 10 and the resin sheet 30 is performed so that a part or the whole of the resin composition layer 31 is filled in the through-hole 14. Therefore, the lamination is usually performed so that the resin composition layer 31 and the core substrate 10 are bonded. Specifically, the lamination can be performed by bonding the resin sheet 30 to the core substrate 10 under heat and pressure, thereby bonding the resin composition layer 31 to the core substrate 10. When the resin sheet 30 has a support 32 as in the example shown in FIG. 4, the lamination can be performed by pressing the resin sheet 30 against the core substrate 10 from the support 32 side. Examples of members used for heat and pressure bonding (hereinafter, sometimes referred to as "heat and pressure bonding members"; not shown) include heated metal plates (e.g., SUS mirror plates) or metal rolls (e.g., SUS rolls). The heat and pressure bonding members may be directly pressed against the resin sheet 30, but it is preferable to press the resin sheet 30 through an elastic material such as heat-resistant rubber so that the resin sheet 30 can sufficiently follow the surface irregularities of the core substrate 10.

[0152] The lamination of the core substrate 10 and the resin sheet 30 may be performed, for example, by a vacuum lamination method. The lamination conditions may be, for example, as follows. The thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably 80°C to 140°C. The thermocompression pressure is preferably in the range of 0.098 MPa to 1.77 MPa, more preferably 0.29 MPa to 1.47 MPa. The thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably 30 seconds to 300 seconds. The lamination is preferably performed under reduced pressure conditions of a pressure of 13 hPa or less.

[0153] After lamination, the laminated resin sheet 30 may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support 32 side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. Note that lamination and smoothing treatment may be performed successively using a vacuum laminator.

[0154] FIG. 5 is a cross-sectional view showing a state where the core substrate 10 and the resin sheet 30 are laminated in the manufacturing method of the circuit board according to the first embodiment of the present invention. By laminating the core substrate 10 and the resin sheet 30, as shown in FIG. 5, the resin composition layer 31 of the resin sheet 30 enters the through-hole 14, so that the through-hole 14 is filled with the resin composition layer 31. Here, an example will be described in which a part of the resin composition layer 31 enters the through-hole 14, and another part does not enter the through-hole 14 and adheres to the first surface 10U of the core substrate 10. Thus, the resin composition layer 31 can be formed on the first surface 10U of the core substrate 10. Furthermore, yet another part of the resin composition layer 31 that has entered the through-hole 14 can pass through the through-hole 14 and be discharged from the opening on the second surface 10D side of the core substrate 10. Thus, the resin composition layer 31 can be formed on the second surface 10D of the core substrate 10.

[0155] Usually, the support 32 is peeled off after lamination of the core substrate 10 and the resin sheet 30. In this embodiment, an example will be described in which the support 32 is peeled off before step (2) after lamination of the core substrate 10 and the resin sheet 30. However, the support 32 may be peeled off after step (2).

[0156] <Process (2)> 6 is a schematic cross-sectional view for explaining step (2) of the method for manufacturing a circuit board according to the first embodiment of the present invention. Step (2) includes, after laminating the core substrate 10 and the resin sheet 30, curing the resin composition layer 31 as shown in FIG. 6. By curing the resin composition layer 31, a magnetic layer 40 containing a cured product of the resin composition can be formed. The magnetic layer 40 is formed in the through-hole 14, and can also be usually formed on the first surface 10U and the second surface 10D of the core substrate 10.

[0157] The resin composition layer 31 is usually cured by thermal curing. The thermal curing conditions of the resin composition layer 31 can be appropriately set within a range in which the curing of the resin composition layer 31 proceeds. The curing temperature is preferably 60°C or higher, more preferably 70°C or higher, and even more preferably 80°C or higher, and is preferably 245°C or lower, more preferably 220°C or lower, and even more preferably 200°C or lower. The curing time is preferably 5 minutes or higher, more preferably 10 minutes or higher, and even more preferably 15 minutes or higher, and is preferably 120 minutes or lower, more preferably 110 minutes or lower, and even more preferably 100 minutes or lower.

[0158] The degree of hardening of the magnetic layer 40 obtained in step (2) is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The degree of hardening can be measured, for example, using a differential scanning calorimeter.

[0159] The method for manufacturing a circuit board may include a step of heating the resin composition layer 31 at a temperature lower than the curing temperature (preheating step) after laminating the core substrate 10 and the resin sheet 30 and before curing the resin composition layer 31. For example, prior to curing the resin composition layer 31, the resin composition layer 31 may be preheated at a temperature of usually 50° C. or higher and lower than 120° C. (preferably 60° C. or higher and 110° C. or lower, more preferably 70° C. or higher and 100° C. or lower) for usually 5 minutes or longer (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes).

[0160] <Process (3)> FIG. 7 is a schematic cross-sectional view for explaining step (3) of the method for manufacturing a circuit board according to the first embodiment of the present invention. Step (3) may include polishing the magnetic layer 40. In detail, step (3) may include polishing the magnetic layer 40 in the portion outside the through-hole 14. In the example shown in this embodiment, the magnetic layer 40 is formed on the first surface 10U and the second surface 10D of the core substrate 10, so that the magnetic layer 40 in the portion on the first surface 10U and the second surface 10D can be polished. The magnetic layer 40 in the portion outside the through-hole 14 is generally an unnecessary surplus portion in the final product. By the above-mentioned polishing, the surplus portion can be removed as shown in FIG. 7. In addition, by polishing, the polished surfaces 40U and 40D as the surfaces of the magnetic layer 40 can be flattened.

[0161] The polishing method may be a method capable of removing unnecessary portions of the magnetic layer 40. Examples of such polishing methods include buff polishing, belt polishing, ceramic polishing, etc. Examples of commercially available buff polishing devices include "NT-700IM" manufactured by Ishii Hyoki Co., Ltd.

[0162] The arithmetic mean roughness (Ra) of the polished surfaces 40U and 40D of the magnetic layer 40 is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving adhesion with the conductor layer (not shown in FIG. 7). The upper limit is preferably 1000 nm or less, more preferably 900 nm or less, and even more preferably 800 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.

[0163] After step (2) and before step (3), the magnetic layer 40 may be subjected to a heat treatment in order to further increase the degree of hardening of the magnetic layer 40. The temperature in the heat treatment may be similar to the hardening temperature described above. The specific heat treatment temperature is preferably 120° C. or higher, more preferably 130° C. or higher, and even more preferably 150° C. or higher, and preferably 245° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. The heat treatment time is preferably 5 minutes or higher, more preferably 10 minutes or higher, and even more preferably 15 minutes or higher, and preferably 150 minutes or lower, more preferably 120 minutes or lower, and even more preferably 100 minutes or lower.

[0164] By carrying out the above-mentioned steps (1) and (2) and further carrying out step (3) as necessary, it is possible to obtain a circuit board 100 including a core substrate 10 and a magnetic layer 40 filling the through-holes 14 of the core substrate 10. The circuit board 100 thus obtained may be subjected to steps (4) and (5) as necessary to form a conductor layer.

[0165] <Process (4)> Step (4) includes subjecting the magnetic layer to a roughening treatment. Typically, the polished surface of the magnetic layer is subjected to the roughening treatment. In step (4), the roughening treatment may be applied not only to the polished surface of the magnetic layer but also to the surfaces 10U and 10D of the core substrate 10.

[0166] The procedure and conditions of the roughening treatment are not particularly limited, and may be, for example, the procedure and conditions used in the manufacturing method of a multilayer printed wiring board. As a specific example, the roughening treatment may be performed by a method including, in this order, a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid.

[0167] Examples of the swelling liquid used in the swelling treatment include an alkaline solution, a surfactant solution, and the like, and an alkaline solution is preferred. As the alkaline solution that is the swelling liquid, a sodium hydroxide solution and a potassium hydroxide solution are more preferred. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan.

[0168] The swelling treatment with a swelling liquid can be carried out, for example, by immersing the magnetic layer for 1 to 20 minutes in a swelling liquid at 30 to 90° C. From the viewpoint of keeping the swelling of the resin contained in the magnetic layer to an appropriate level, it is preferable to immerse the magnetic layer in a swelling liquid at 40 to 80° C. for 5 to 15 minutes.

[0169] An example of an oxidizing agent used in the roughening treatment is an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably carried out by immersing the magnetic layer in a solution of the oxidizing agent heated to 60°C to 80°C for 10 to 30 minutes. The concentration of the permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact P" and "Dosing Solution Securigans P" manufactured by Atotech Japan.

[0170] The neutralizing liquid that can be used for the neutralization treatment is preferably an acidic aqueous solution. An example of a commercially available neutralizing liquid is "Reduction Solution Securigans P" manufactured by Atotech Japan. The neutralization treatment using the neutralizing liquid can be performed by immersing the treated surface that has been roughened with an oxidizing solution in a neutralizing liquid at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method of immersing the magnetic layer that has been roughened with an oxidizing solution in a neutralizing liquid at 40°C to 70°C for 5 to 20 minutes is preferred.

[0171] The arithmetic mean roughness (Ra) of the magnetic layer after the surface roughening treatment is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving the adhesion with the conductor layer. The upper limit is preferably 1500 nm or less, more preferably 1200 nm or less, and even more preferably 1000 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.

[0172] <Process (5)> Fig. 8 is a schematic cross-sectional view for explaining step (5) of the method for manufacturing the circuit board 100 according to the first embodiment of the present invention. Step (5) includes forming a conductor layer 50 on the ground surfaces 40U and 40D of the magnetic layer 40, as shown in Fig. 8. In this embodiment, an example is shown in which the conductor layer 50 is formed not only on the ground surfaces 40U and 40D of the magnetic layer 40, but also on the surrounding surfaces (for example, the first surface 10U and the second surface 10D of the core substrate 10). Also, Fig. 8 shows an example in which the conductor layer 50 is formed on both sides of the core substrate 10, but the conductor layer 50 may be formed on only one side of the core substrate 10.

[0173] 9 is a schematic cross-sectional view for explaining step (5) of the method for manufacturing the circuit board 100 according to the first embodiment of the present invention. As shown in FIG. 9, step (5) may include forming a conductor layer 50, and then removing the conductor layer 50, the metal layers 12 and 13, and a part of the plating layer 20 by a process such as etching to form a pattern conductor layer 51.

[0174] The conductor layer 50 can be formed by, for example, plating, sputtering, vapor deposition, etc., with plating being preferred. In a preferred embodiment, the surface of the magnetic layer 40 (and, if necessary, the core substrate 10) can be plated by an appropriate method such as a semi-additive method or a full-additive method to form a patterned conductor layer 51 having a desired wiring pattern. Examples of materials for the conductor layer 50 include single metals such as gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium; and alloys of two or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. Among these, from the viewpoints of versatility, cost, ease of patterning, and the like, it is preferable to use chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy, it is more preferable to use chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or a nickel-chromium alloy, and it is even more preferable to use copper.

[0175] Here, an example of a method for forming the patterned conductor layer 51 will be described in detail. A plating seed layer is formed on the polished surfaces 40U and 40D of the magnetic layer 40 by electroless plating. Next, a mask pattern is formed on the formed plating seed layer as necessary, and then an electrolytic plating layer is formed by electrolytic plating. Thereafter, the mask pattern is removed as necessary, and unnecessary plating seed layer is further removed by a process such as etching, to form the patterned conductor layer 51 having a desired wiring pattern. After the formation of the patterned conductor layer 51, an annealing treatment may be performed as necessary to improve the adhesion strength of the patterned conductor layer 51. The annealing treatment can be performed, for example, by heating at 150°C to 200°C for 20 minutes to 90 minutes.

[0176] The thickness of the patterned conductor layer 51 is preferably 1 μm or more, more preferably 3 μm or more, even more preferably 5 μm or more, and is preferably 70 μm or less, more preferably 50 μm or less, even more preferably 40 μm or less, and particularly preferably 10 μm or less.

[0177] By the above method, a circuit board 100 including a magnetic layer 40 is obtained. The magnetic layer 40 is obtained by curing the resin composition layer 31, and therefore contains a cured product of the resin composition. Therefore, the magnetic layer 40 can contain a large amount of magnetic powder (not shown), and therefore can have excellent magnetic properties.

[0178] <Second embodiment> The circuit board of the second embodiment includes a magnetic layer formed of a cured product of a resin composition layer of a resin sheet. (A) a step of laminating a resin sheet onto an inner layer substrate such that the resin composition layer is bonded to the inner layer substrate to form a magnetic layer; Includes.

[0179] Furthermore, the method for producing a circuit board according to the second embodiment may include any step in addition to step (A). For example, the method for producing a circuit board may include the following steps: (B) a step of drilling holes in the magnetic layer; (C) a step of subjecting the magnetic layer to a roughening treatment; and (D) forming a conductor layer on the magnetic layer; This production method preferably includes steps (A) to (D) in this order.

[0180] <Process (A)> Step (A) is a step of laminating a resin sheet on an inner layer substrate so that the resin composition layer is bonded to the inner layer substrate to form a magnetic layer. In one embodiment of step (A), a resin sheet is laminated on an inner layer substrate so that the resin composition layer is bonded to the inner layer substrate, and the resin composition layer is thermally cured to form a magnetic layer.

[0181] 10 is a schematic cross-sectional view illustrating step (A) of the method for producing a circuit board according to the second embodiment of the present invention. In step (A), a resin sheet 310 including a support 330 and a resin composition layer 320a provided on the support 330 is laminated on an inner substrate 200 such that the resin composition layer 320a is bonded to the inner substrate 200.

[0182] The inner layer substrate 200 is an insulating substrate. Examples of materials for the inner layer substrate 200 include insulating base materials such as a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The inner layer substrate 200 may be an inner layer circuit substrate having wiring and the like built into its thickness.

[0183] As shown in Fig. 10 as an example, the inner layer substrate 200 has a first conductor layer 420 provided on the first main surface 200a and an external terminal 240 provided on the second main surface 200b. The first conductor layer 420 may include a plurality of wirings. In the illustrated example, only the wirings constituting the coil-shaped conductive structure 400 of the inductor element are shown. The external terminal 240 is a terminal for electrically connecting to an external device or the like (not shown). The external terminal 240 can be configured as a part of the conductor layer provided on the second main surface 200b.

[0184] The conductive material that can form the first conductive layer 420 and the external terminals 240 is similar to the material of the conductive layer explained in the section “<Step (5)>” of the first embodiment.

[0185] The first conductor layer 420 and the external terminal 240 may have a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different types of metals or alloys are laminated. The thickness of the first conductor layer 420 and the external terminal 240 is the same as that of the second conductor layer 440 described later.

[0186] The line (L) / space (S) ratio of the first conductor layer 420 and the external terminal 240 is not particularly limited, but from the viewpoint of obtaining a magnetic layer with excellent smoothness by reducing surface irregularities, it is usually 900 / 900 μm or less, preferably 700 / 700 μm or less, more preferably 500 / 500 μm or less, even more preferably 300 / 300 μm or less, and even more preferably 200 / 200 μm or less. The lower limit of the line / space ratio is not particularly limited, but from the viewpoint of improving embedding of the resin composition layer in the space, it is preferably 1 / 1 μm or more.

[0187] The inner layer substrate 200 may have a plurality of through holes 220 penetrating the inner layer substrate 200 from the first main surface 200a to the second main surface 200b. The through holes 220 are provided with through hole wiring 220a. The through hole wiring 220a electrically connects the first conductor layer 420 and the external terminal 240.

[0188] The resin composition layer 320a and the inner substrate 200 are joined together in the same manner as the lamination method of the core base material and the resin sheet described in the section "<Step (1)>" of the first embodiment.

[0189] After the resin sheet is laminated on the inner layer substrate, the resin composition layer is thermally cured to form a magnetic layer. As shown in an example in FIG. 11, the resin composition layer 320a bonded to the inner layer substrate 200 is thermally cured to form the first magnetic layer 320.

[0190] The thermal curing conditions for the resin composition layer 320a are the same as those for the resin composition layer described in the section “<Step (2)>” of the first embodiment.

[0191] The support 330 may be removed between the end of the thermal curing in step (A) and step (B), or may be peeled off after step (B).

[0192] <Process (B)> 12 is a schematic cross-sectional view illustrating step (B) of the method for manufacturing a circuit board according to the second embodiment of the present invention. In step (B), a hole is drilled in the first magnetic layer 320 to form a via hole 360.

[0193] The via hole 360 ​​serves as a path for electrically connecting the first conductor layer 420 and the second conductor layer 440 described below. The via hole 360 ​​may be formed using, for example, a drill, a laser, plasma, or the like, depending on the composition of the resin composition used to form the magnetic layer. The dimensions and shape of the via hole may be appropriately determined depending on the design of the circuit board.

[0194] <Process (C)> Step (C) includes performing a roughening treatment on the magnetic layer with the via holes formed therein. The roughening treatment method in step (C) can be the same as that described in the section "<Step (4)>" of the first embodiment.

[0195] The roughening treatment in step (C) may be a treatment for polishing the surface of the insulating layer. The polishing method may be the same as that described in the section "<Step (3)>" of the first embodiment.

[0196] The arithmetic mean roughness (Ra) of the roughened surface of the magnetic layer is preferably 300 nm or more, more preferably 350 nm or more, and even more preferably 400 nm or more, from the viewpoint of improving plating adhesion. The upper limit is preferably 1000 nm or less, more preferably 900 nm or less, and even more preferably 800 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.

[0197] <Process (D)> 13 is a schematic cross-sectional view for explaining step (D) of the method for manufacturing a circuit board according to the second embodiment of the present invention. Step (D) includes forming a second conductor layer 440 on the first magnetic layer 320, as shown in an example in FIG.

[0198] The conductive material that can form the second conductive layer 440 is similar to the material of the conductive layer explained in the section “<Step (5)>” of the first embodiment.

[0199] From the viewpoint of thinning, the thickness of the second conductor layer 440 is preferably 70 μm or less, more preferably 60 μm or less, even more preferably 50 μm or less, even more preferably 40 μm or less, particularly preferably 30 μm or less, 20 μm or less, 15 μm or less, or 10 μm or less. The lower limit is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 5 μm or more.

[0200] The second conductor layer 440 can be formed by plating. The second conductor layer 440 is preferably formed by a wet plating method such as a semi-additive method or a full-additive method including an electroless plating process, a mask pattern forming process, an electrolytic plating process, and a flash etching process. By forming the second conductor layer 440 using a wet plating method, it is possible to form the second conductor layer 440 including a desired wiring pattern. Note that this process also forms an in-via-hole wiring 360a in the via hole 360.

[0201] The first conductor layer 420 and the second conductor layer 440 may be provided in a spiral shape, for example, as shown in Figs. 14 to 16 described later. In one example, one end of the spiral wiring portion of the second conductor layer 440 on the center side is electrically connected to one end of the spiral wiring portion of the first conductor layer 420 on the center side by the via-hole wiring 360a. The other end of the spiral wiring portion of the second conductor layer 440 on the outer periphery side is electrically connected to the land 420a of the first conductor layer 42 by the via-hole wiring 360a. Therefore, the other end of the spiral wiring portion of the second conductor layer 440 on the outer periphery side is electrically connected to the external terminal 240 via the via-hole wiring 360a, the land 420a, and the through-hole wiring 220a.

[0202] The coil-shaped conductive structure 400 is composed of a spiral wiring portion that is a part of the first conductor layer 420, a spiral wiring portion that is a part of the second conductor layer 440, and via-hole wiring 360a that electrically connects the spiral wiring portion of the first conductor layer 420 and the spiral wiring portion of the second conductor layer 440.

[0203] After step (D), a step of forming a magnetic layer on the conductor layer may be performed. In detail, as shown in an example in Fig. 15, a second magnetic layer 340 is formed on the first magnetic layer 320 on which the second conductor layer 440 and the via-hole wiring 360a are formed. The second magnetic layer may be formed by the same steps as those already described.

[0204] [Inductor components] The inductor component includes the circuit board of the present invention. When such an inductor component includes a circuit board obtained by the method for producing a circuit board according to the first embodiment, the inductor component has an inductor pattern formed by a conductor at least in a part around the cured product of the resin composition layer. For example, the inductor component described in JP 2016-197624 A can be used.

[0205] Furthermore, when the inductor substrate includes a circuit board obtained by the circuit board manufacturing method of the second embodiment, the inductor substrate has a magnetic layer and a conductive structure at least partially embedded in the magnetic layer, and includes an inductor element formed by the conductive structure and a part of the magnetic layer that extends in the thickness direction of the magnetic layer and is surrounded by the conductive structure. Here, Fig. 14 is a schematic plan view of the inductor substrate having the inductor element as viewed from one side in the thickness direction. Fig. 15 is a schematic view showing a cut end surface of the inductor substrate cut at the position indicated by the dashed line II-II in Fig. 14. Fig. 16 is a schematic plan view for explaining the configuration of a first conductive layer of the inductor substrate.

[0206] 14 and 15, the circuit board 100 is a build-up wiring board having a plurality of magnetic layers (first magnetic layer 320, second magnetic layer 340) and a plurality of conductor layers (first conductor layer 420, second conductor layer 440), i.e., a build-up magnetic layer and a build-up conductor layer. The inductor board 100 also includes an inner layer board 200.

[0207] 15, the first magnetic layer 320 and the second magnetic layer 340 constitute the magnetic part 300 which can be seen as an integrated magnetic layer. Therefore, the coiled conductive structure 400 is provided so that at least a portion thereof is embedded in the magnetic part 300. That is, in the inductor substrate 100 of this embodiment, the inductor element is constituted by the coiled conductive structure 400 and a core portion which is a portion of the magnetic part 300 that extends in the thickness direction of the magnetic part 300 and is surrounded by the coiled conductive structure 400.

[0208] 16, the first conductor layer 420 includes a spiral wiring portion for constituting the coil-shaped conductive structure 400, and a rectangular land 420a electrically connected to the through-hole wiring 220a. In the illustrated example, the spiral wiring portion includes a straight portion and a bent portion that is bent at a right angle, and a detour portion that detours around the land 420a. In the illustrated example, the spiral wiring portion of the first conductor layer 420 has an overall outline that is approximately rectangular, and has a shape that winds counterclockwise from the center toward the outside.

[0209] Similarly, a second conductor layer 440 is provided on the first magnetic layer 320. The second conductor layer 440 includes a spiral wiring portion for configuring the coil-shaped conductive structure 400. In Fig. 14 or 15, the spiral wiring portion includes a straight portion and a bent portion bent at a right angle. In Fig. 14 or 15, the spiral wiring portion of the second conductor layer 440 has an overall outline that is substantially rectangular, and has a shape that is wound clockwise from the center toward the outside.

[0210] Such an inductor component can be used as a wiring board for mounting electronic components such as semiconductor chips, and can also be used as a (multilayer) printed wiring board using such a wiring board as an inner layer substrate.Furthermore, such a wiring board can be used as an individual chip inductor component, and can also be used as a surface-mounted printed wiring board.

[0211] In addition, various types of semiconductor devices can be manufactured using such a wiring board. The semiconductor device including such a wiring board can be suitably used in electric products (e.g., computers, mobile phones, digital cameras, televisions, etc.) and vehicles (e.g., motorcycles, automobiles, trains, ships, aircraft, etc.). EXAMPLES

[0212] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following description, the terms "parts" and "%" used to express amounts refer to "parts by mass" and "% by mass", respectively, unless otherwise specified.

[0213] <Measurement of pH of dispersant (indicator method)> Dispersants were dissolved in acetone to prepare measurement samples (22°C) with a dispersant concentration of 0.1 g / mL. pH test paper was gently immersed in the solution and then removed to dry off excess water. The color of the wet part of the test paper was compared with the color sample, and the pH of the closest color was determined as the pH of each sample.

[0214] <Synthesis Example 1: Synthesis of Dispersant 1> In a reaction flask equipped with a thermometer, a stirrer, a nitrogen inlet, and a reflux tube, 10.0 parts of 12-hydroxystearic acid (manufactured by Junsei Chemical Co., Ltd.) and 190 parts of ε-caprolactone (manufactured by Junsei Chemical Co., Ltd.) were charged, and the temperature was raised to 160°C over 4 hours under a nitrogen stream, and after heating at 160°C for 2 hours, heating was continued until the remaining amount of ε-caprolactone was 1% or less. Then, the mixture was cooled to room temperature. Hereinafter, this reaction liquid is referred to as dispersant 1. Dispersant 1 had the characteristics of a weight average molecular weight of 23,000 and an acid value of 9.0 mgKOH / g. The pH was 5 by the indicator method.

[0215] <Synthesis Example 2: Synthesis of Dispersant 2> In a reaction flask equipped with a thermometer, a stirrer, a nitrogen inlet, and a reflux tube, 10.0 parts of 12-hydroxystearic acid (manufactured by Junsei Chemical Co., Ltd.) and 180 parts of δ-valerolactone (manufactured by Tokyo Chemical Industry Co., Ltd.) were charged, and the temperature was raised to 160°C over 4 hours under a nitrogen stream, and after heating at 160°C for 2 hours, heating was continued until the remaining amount of δ-valerolactone was 1% or less. Then, the mixture was cooled to room temperature. Hereinafter, this reaction liquid is referred to as dispersant 2. Dispersant 2 had the characteristics of a weight average molecular weight of 22,000 and an acid value of 8.9 mgKOH / g. The pH was 5 by the indicator method.

[0216] <Synthesis Example 3: Synthesis of Dispersant 3> A mixture of 25.0 parts of xylene and 70 parts of a 10% aqueous solution of polyallylamine ("PAA-1LV" manufactured by Nitto Boseki Co., Ltd., number average molecular weight approximately 3,000) was stirred at 160°C in a reaction flask equipped with a thermometer, a stirrer, a nitrogen inlet, and a reflux condenser. Water was distilled off using a separator, and while the xylene was returned to the reaction solution, 114.21 parts of the dispersant obtained in Synthesis Example 1, which had been heated to 160°C, was added thereto, and the reaction was carried out at 160°C for 2 hours. The mixture was further heated at 160°C for 4 hours, and the xylene was distilled off at 160°C to obtain Dispersant 3. Dispersant 3 had an amine value of 31.0 mg KOH / g. The amine value immediately after mixing was 312.6 mg KOH / g. The pH was 6 by the indicator method.

[0217] <Synthesis Example 4: Synthesis of Dispersant 4> In a reaction flask equipped with a thermometer, a stirrer, a nitrogen inlet, a reflux condenser and a water separator, 30.0 parts of xylene (manufactured by Junsei Chemical Co., Ltd.), 300.0 parts of 12-hydroxystearic acid (manufactured by Junsei Chemical Co., Ltd.) and 0.1 parts of tetrabutyl titanate (manufactured by Tokyo Chemical Industry Co., Ltd.) were charged and heated to 160°C over 4 hours under a nitrogen stream. The mixture was further heated at 160°C for 4 hours, and xylene was distilled off at 160°C to obtain dispersant 4. Dispersant 4 had a weight average molecular weight of 6000 and an acid value of 23.0 mgKOH / g. The pH was 5 by the indicator method.

[0218] <Synthesis Example 5: Synthesis of Dispersant 5> In a reaction flask equipped with a thermometer, a stirrer, a nitrogen inlet, a reflux condenser and a water separator, 30.0 parts of xylene (manufactured by Junsei Chemical Co., Ltd.), 300.0 parts of 12-hydroxystearic acid (manufactured by Junsei Chemical Co., Ltd.) and 0.1 parts of tetrabutyl titanate (manufactured by Tokyo Chemical Industry Co., Ltd.) were charged and heated to 160°C over 4 hours under a nitrogen stream. The mixture was further heated at 160°C for 4 hours (the acid value at this time was about 20 mgKOH / g), and the xylene was distilled off at 160°C. The mixture was then cooled to room temperature, and the water generated during the heating reaction was separated from the xylene in the distillate, and the xylene was returned to the reaction solution. This reaction solution is called polyester PE-1. In a reaction flask equipped with a thermometer, a stirrer, a nitrogen inlet, a reflux tube and a water separator, a mixture consisting of 25.0 parts of xylene and 70 parts of a 10% aqueous solution of polyallylamine ("PAA-1LV" manufactured by Nitto Boseki Co., Ltd., number average molecular weight approximately 3,000) was stirred at 160 ° C., water was distilled off using a separator, and 2.5 parts of polyester PE-1 was added to the reaction solution while xylene was returned to the reaction solution, and the reaction was carried out at 160 ° C. for 2 hours. The mixture was further heated at 160 ° C. for 4 hours, and xylene was distilled off at 160 ° C. Dispersant 5 had a polyester skeleton in which R in the general formula (1) is an alkylene group having 11 carbon atoms, and had the characteristics of an amine value of 38.5 mg KOH / g and an acid value of 23.5 mg KOH / g. The amine value of dispersant 5 immediately after mixing was 317 mg KOH / g. The pH of dispersant 5 by the indicator method was 6.

[0219] <Example 1: Production of magnetic varnish 1> Epoxy resin ("ZX-1059", a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin, manufactured by Nippon Steel Chemical & Material Co., Ltd.) 2.41 parts by mass, triazine skeleton-containing phenolic resin ("LA-7054", manufactured by DIC Corporation, a 60% solids solution with a hydroxyl group equivalent of approximately 125) 2.74 parts by mass, phenoxy resin ("YL7553BH30", manufactured by Mitsubishi Chemical Corporation, a 30% solids solution with a hydroxyl group equivalent of approximately 125) K and cyclohexanone) 2.39 parts by mass, dispersant 1 (dispersant synthesized in Synthesis Example 1, polyester dispersant with 5 carbon atoms) 0.5 parts by mass, solvent (cyclohexanone) 3.0 parts by mass, imidazole-based curing accelerator ("2E4MZ", 2-ethyl-4-methylimidazole, manufactured by Shikoku Chemical Industry Co., Ltd.) 0.02 parts by mass, magnetic powder ("M03S", Fe-Mn-based ferrite, average particle size 0.4 μm, specific gravity 5.1 m 2 Magnetic varnish 1 was prepared by mixing 27.91 parts by mass of magnetic powder (MA-RCO-24, Fe-Ni alloy, average particle size 3.0 μm, manufactured by DOWA Electronics Co., Ltd.) and 93.19 parts by mass of magnetic powder (MA-RCO-24 ... Fe-Ni alloy, average particle size 3.0 μm, manufactured by DOWA Electronics Co., Ltd.)

[0220] <Example 2: Preparation of magnetic varnish 2> In Example 1, the content of Dispersant 1 (the dispersant synthesized in Synthesis Example 1, a polyester dispersant having 5 carbon atoms) was changed from 0.5 parts by mass to 1 part by mass. Magnetic varnish 2 was prepared in the same manner as in Example 1 except for the above.

[0221] <Example 3: Preparation of magnetic varnish 3> In Example 1, the content of Dispersant 1 (the dispersant synthesized in Synthesis Example 1, a polyester dispersant having 5 carbon atoms) was changed from 0.5 parts by mass to 0.1 parts by mass. Magnetic varnish 3 was prepared in the same manner as in Example 1 except for the above.

[0222] <Example 4: Preparation of magnetic varnish 4> In Example 1, 0.5 parts by mass of Dispersant 1 (the dispersant synthesized in Synthesis Example 1, a polyester dispersant having 5 carbon atoms) was changed to 0.5 parts by mass of Dispersant 2 (the dispersant synthesized in Synthesis Example 2, a polyester dispersant having 4 carbon atoms). Magnetic varnish 4 was prepared in the same manner as in Example 1, except for the above.

[0223] <Example 5: Preparation of magnetic varnish 5> In Example 1, 0.5 parts by mass of Dispersant 1 (dispersant synthesized in Synthesis Example 1, a polyester dispersant having 5 carbon atoms) was changed to 0.5 parts by mass of Dispersant 3 (dispersant synthesized in Synthesis Example 3, a dispersant containing a polyester having 5 carbon atoms). Magnetic varnish 5 was prepared in the same manner as in Example 1 except for the above.

[0224] <Example 6: Preparation of magnetic varnish 6> In Example 1, magnetic powder ("M03S", Fe-Mn ferrite, average particle size 0.4 μm, specific gravity 5.1 μm) was used. 2 / g, Powdertech Co., Ltd.) was added to 27.91 parts by mass of magnetic powder ("MZ03S", Fe-Mn-Zn ferrite, average particle size 0.4 μm, specific gravity 5.1 m 2 The amount of cellulose acetate solution used was changed to 27.91 parts by mass / g (manufactured by Powder Tech Co., Ltd.) Magnetic varnish 6 was prepared in the same manner as in Example 1 except for the above points.

[0225] <Comparative Example 1: Preparation of Magnetic Varnish 7> In Example 1, 0.5 parts by mass of Dispersant 1 (dispersant synthesized in Synthesis Example 1, polyester dispersant having 5 carbon atoms) was changed to 0.5 parts by mass of Dispersant 4 (dispersant synthesized in Synthesis Example 4, polyester dispersant having 11 carbon atoms, Synthesis Example 4). Magnetic varnish 7 was prepared in the same manner as in Example 1 except for the above.

[0226] <Comparative Example 2: Preparation of Magnetic Varnish 8> In Example 1, 0.5 parts by mass of Dispersant 1 (dispersant synthesized in Synthesis Example 1, a polyester dispersant having 5 carbon atoms) was changed to 0.5 parts by mass of Dispersant 5 (dispersant synthesized in Synthesis Example 5, a dispersant containing a polyester having 11 carbon atoms). Magnetic varnish 8 was prepared in the same manner as in Example 1 except for the above points.

[0227] <Comparative Example 3: Preparation of Magnetic Varnish 9> In Example 1, 0.5 parts by mass of dispersant 1 (the dispersant synthesized in Synthesis Example 1, a polyester dispersant having 5 carbon atoms) was changed to 0.5 parts by mass of dispersant (ED-152, a dispersant without a polyester skeleton, manufactured by Kusumoto Chemicals Co., Ltd.). Magnetic varnish 9 was prepared in the same manner as in Example 1 except for the above.

[0228] <Comparative Example 4: Preparation of Magnetic Varnish 10> In Example 1, 0.5 parts by mass of dispersant 1 (the dispersant synthesized in Synthesis Example 1, a polyester dispersant having 5 carbon atoms) was changed to 0.5 parts by mass of dispersant (SC-1015F, a dispersant without a polyester skeleton, manufactured by NOF Corporation). A magnetic varnish 10 was prepared in the same manner as in Example 1, except for the above points.

[0229] <Preparation of Resin Sheet> The magnetic varnishes prepared in the examples and comparative examples were applied using a die coater onto a PET film (Toray Industries, Inc., "Lumirror R80", thickness 38 μm, softening point 130°C, hereinafter sometimes referred to as "release PET") that had been release-treated with an alkyd resin-based release agent (Lintec Corporation, "AL-5"), so that the thickness of the resin composition layer after drying was 100 μm. The film was then dried at 65°C to 115°C (average 100°C) for 7 minutes to obtain a resin sheet.

[0230] <Preparation of sheet-shaped cured product> The resin sheet was cut into 200 mm squares. The cut resin sheet (200 mm square) was laminated onto one side of a polyimide film (Ube Industries' "Upilex 25S", 25 μm thick, 240 mm square) using a batch-type vacuum pressure laminator (Nikko Materials' two-stage build-up laminator "CVP700"). The resin composition layer was in contact with the center of the smooth surface of the polyimide film (Ube Industries' "Upilex 25S", 25 μm thick, 240 mm square). The lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing at 100 ° C. and a pressure of 0.74 MPa for 30 seconds. This resulted in a multilayer film having a layer structure of support / resin composition layer / polyimide film. After peeling off the support, the resin composition layer was heat-cured by heating at 190 ° C. for 90 minutes. The polyimide film was then peeled off to obtain a sheet-like cured product of the resin composition.

[0231] <Measurement of relative permeability and magnetic loss> The obtained sheet-like cured product was cut into an evaluation sample having a width of 5 mm and a length of 18 mm. The evaluation sample was measured for relative permeability (μ') and magnetic loss (μ'') by a 3-turn coil method using an Agilent Technologies ("HP8362B" manufactured by Agilent Technologies) at a measurement frequency of 50 MHz and a room temperature of 23°C. The magnetic loss was calculated by the following formula "tan δ=μ' / μ''". The relative permeability was evaluated according to the following criteria. ○: Relative permeability is 20 or more ×: Relative permeability is less than 20

[0232] <Measurement of mechanical strength (tensile breaking strength)> The tensile breaking strength of the obtained sheet-like cured product was measured in accordance with JIS K 7127. The measurement results were evaluated according to the following criteria. ○: 60MPa or more ×: Less than 60MPa

[0233] [Table 1] [Explanation of symbols]

[0234] 10 Core substrate 10U front page 10D second side 11 Support substrate 12 metal layer 13 Metal layer 14 through hole 20 Plating layer 30 Resin sheet 31 Resin composition layer 32 Support 40 Magnetic layer 40U polished surface 40D polished surface 50 Conductor Layer 51 Patterned conductor layer 100 Circuit Board 200 Inner layer board 200a 1st main surface 200b 2nd main surface 220 through hole 220a Through hole wiring 240 External terminal 300 Magnetic part 310 Resin sheet 320a Resin composition layer 320 First insulating layer 330 Support 340 Second insulating layer 360 Beer Hall 360a via hole wiring 400 Coil-shaped conductive structure 420 First conductor layer 420a Land 440 Second conductor layer

Claims

1. A resin sheet having a support and a resin composition layer formed from a resin composition provided on the support, The resin composition comprises: (A) magnetic powder, (B) an epoxy resin, (C) a dispersant, (D) a curing agent, and (E) a thermoplastic resin, A resin sheet, wherein the component (C) has a polyester skeleton represented by the following general formula (1): 【Chemistry 1】 (In general formula (1), R each independently represents a divalent hydrocarbon group having 2 to 10 carbon atoms, and n represents an integer of 2 to 1,000.)

2. The resin sheet according to claim 1 , wherein the content of the component (C) is 0.1% by mass or more and 5% by mass or less, based on 100% by mass of non-volatile components in the resin composition.

3. The resin sheet according to claim 1 or 2, wherein the component (A) comprises (A-1) a magnetic powder having an average particle size of 1 μm or more, and (A-2) a magnetic powder having an average particle size of less than 1 μm.

4. The resin sheet according to any one of claims 1 to 3, wherein the component (A) includes (A-1) a magnetic powder having an average particle size of 1 μm or more and 10 μm or less, and (A-2) a magnetic powder having an average particle size of 0.005 μm or more and less than 1 μm.

5. The resin sheet according to any one of claims 1 to 4, wherein the component (A) is at least one selected from the group consisting of iron oxide powder and iron alloy metal powder.

6. The resin sheet according to any one of claims 1 to 5, wherein the component (A) contains iron oxide powder, and the iron oxide powder contains ferrite containing at least one selected from Ni, Cu, Mn, and Zn.

7. The resin sheet according to any one of claims 1 to 6, wherein the content of the component (A) is 70% by mass or more and 98% by mass or less, when the content of the non-volatile components in the resin composition is 100% by mass.

8. The resin sheet according to any one of claims 1 to 7, wherein the mass of the thermoplastic resin (E) when the nonvolatile components in the resin composition are 100% by mass is E1, and the mass of the epoxy resin (B) when the nonvolatile components in the resin composition are 100% by mass is B1, and B1 / E1 is 0.1 or more and 5 or less.

9. The resin sheet according to any one of claims 1 to 8, which is for forming a magnetic layer of a circuit board.

10. The resin sheet according to any one of claims 1 to 9, which is for filling through holes.

11. A circuit board comprising a magnetic layer which is a cured product of a resin composition layer of the resin sheet according to any one of claims 1 to 10.

12. A substrate having a through hole formed therein and a magnetic layer filled in the through hole, A circuit board, wherein the magnetic layer comprises a cured product of a resin composition layer of the resin sheet according to any one of claims 1 to 10.

13. An inductor component comprising the circuit board according to claim 11 or 12.

14. (A) magnetic powder, (B) an epoxy resin, (C) a dispersant, (D) a curing agent, and (E) A resin composition containing a thermoplastic resin, when the mass of the thermoplastic resin (E) is defined as E1 when the nonvolatile components in the resin composition are 100 mass%, and the mass of the epoxy resin (B) is defined as B1 when the nonvolatile components in the resin composition are 100 mass%, B1 / E1 is 0.1 or more and 5 or less, A resin composition, wherein the component (C) has a polyester skeleton represented by the following general formula (1): 【Chemistry 2】 (In general formula (1), R each independently represents a divalent hydrocarbon group having 2 to 10 carbon atoms, and n represents an integer of 2 to 1,000.)

15. A circuit board comprising a magnetic layer which is a cured product of the resin composition according to claim 14.

16. A circuit board comprising: a substrate having a through hole; and a cured product of the resin composition according to claim 14 filled in the through hole.

17. An inductor component comprising the circuit board according to claim 15 or 16.

Citation Information

Patent Citations

  • Dispersion of magnetic material fine grain, manufacture, magnetic recording medium, dispersant and manufacture

    JP1985191023A

  • Resin for dispersion containing polyether / polyester

    JP2006206902A

  • Magnetic composite particles, magnetic carrier, and developer

    JP2010237604A

  • Magnetic sheet

    JP2014127624A

  • Resin sheet and inductor component

    JP2016174142A